Chemical constituents from the aerial parts of Clematis terniflora DC - Meng-Ya Chen; Zi-Han Zhu; Xin-Yu Yu; Ya-Ru Wu; Shi-Hui Qian; Zhen-Lin Li (Biochemical Systematics and Ecology, 2027)

Chemical constituents of Clerodendrum mandarinorum and their chemotaxonomic significance - Shi-Ya Tian; Feng Li; Huai-Qin Liu; Yu Qiu; Wu-Feng Li; Guang-Yan Liang; Chun-Chun Wang; Xue-Long Yan; Shang-Gao Liao; Qin-Feng Zhu (Biochemical Systematics and Ecology, 2026)

L-Arginine effectively alleviates doxorubicin-induced cardiac dysfunction by inhibiting myocardial fibrosis - Mo-li Zhu; Rui Hao; Meng-yao Zhao; Pei-yao Liu; Hong-dou Zhang; Peng Li; Ya-ling Yin; Hui-jun Liu; Guang-qiu Ren; Jie Zhang; Jing Yang (Molecular Biology Reports, 2026)

Small-molecule amine-templated supertetrahedral cluster-based zeolite-type sulfide for efficient Eu3+ ion exchange - Wei-An Li; Yu-Hang Li; Wen-Xuan Li; Ya-Ying Li; Zi-Hao Chen; Xiang Huang; Ming-Zhu Zhang; Fang-Zhen Wang (Journal of Water Process Engineering, 2026)

Temperature-responsive topology regulation for fire-safe, high-strength polyamide 66 via a low-barrier phosphonate spacer - Qin Zhang; Guo-Rui Zhu; Xiang-Xin Xiao; Ya-Dong Wang; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2026)

Rapid temperature flips accelerate and amplify winter hypoxia and internal loading in a reservoir at the tropic of cancer - Ya Zhu; Yiping Li; Yu Chen; Yaning Wang; Daobin Ji; Xingxing Zhao; Carlo Gualtieri; Martin Schmid (Journal of Hydrology, 2026)

Environmental cadmium disrupts placental angiogenesis and fetal growth via enhancing m6A modification in Wwp2 - Cheng-Fang Sun; Ye-Xin Luo; Xin-Xin Zhang; Rui Pan; Yu-Xi Wu; Jia-Ying Chen; Xin-Run Wang; Lan-Lan Wu; Si-Ting Liu; Wei Chang; Zhi Yuan; Da-Min Zhu; et al. (Environmental Pollution, 2026)

Toward understanding tidal flat regime shifts: Contrasting hydro-sediment dynamics revealed by paired observations of two tidal flats - Shibing Zhu; Ya Ping Wang; Yuan Li; Qingguang Zhu; Fei Xing; Mingliang Li; Chao Gao; Shucun Sun (Journal of Hydrology, 2026)

Inhibition of thermal formation of advanced glycation end products and acrylamide by gluten-bound betulonic acid and alphitolic acid: Mechanistic insights from spectroscopy and computation - Qiangqiang Zhu; Yi Le; Chenxia Zhang; Lihui Feng; Hemei Yuan; Yufang Li; Hongkang Zhu; Qiulan Li; Jia Liu; Huanhuan Xu; Ya Wang; Jun Sheng; et al. (Food Research International, 2026)

Residential greenness and incident type 2 diabetes: A large prospective cohort study in China integrating evidence from 17 global cohorts - Jian-Cheng Jiang; Chuan-Jiang He; Ai-Min Xu; Lu Wang; Xiao-Qi Zhu; Bei-Bei Li; Wen Liu; Ya Qiu; Jing-Ran Xu; Min-Hui Li; Zhuo-Hao Wang; Xiao-Guang Zou; et al. (Environmental Research, 2026)

Pre-lithiation strategy enhancing interfacial stability of carbon-coated SiO anodes via controlled formation of LixSiyOz for high-energy lithium-ion batteries - Hong Dong; Yanping Ma; Xiaobin Zhou; Jinying Hou; Juan Xin; Mingzhu Wei; Jianyao Zhu; Shiyou Li; Ya-Jun Cheng (Chemical Engineering Journal, 2026)

Creation of water management systems and social sustainability: exploring millennial human–spring relationships in semi-arid North China - Teligeer Bao; Adrian D. Werner; John Schofield; Yongze Song; Geng Li; Ziyue Zhu; Yonghong Hao; Long Xing; Ya Zhou; Wenjing Liu; Yu-Li Wang (Hydrological Sciences Journal, 2026)

Granulosa cell dysfunction is associated with MCU-mediated mitochondrial calcium dyshomeostasis and reduced AKT phosphorylation in porcine cystic follicles - Yan-Zhu Chen; Ya-Nan Sun; Bo-Qi Zhang; Jin-Xin Zong; Yu-Xin Luo; Si-Hui Wang; Ya-Qiu Li; Hong Hao; Xu Zhou; Lu Chen; Chun-Jin Li (Theriogenology, 2026)

Waste cotton textiles-derived cellulose superhydrophobic aerogel for efficient oil-water separation - Ya-hui Li; Hui-Jiang; Xiao-quan Zhu; Ru-ru Ma; Er-min Zhou; Jun-li Luo; De-qiang Li; Hong-tao Jia; Jun Li; Lu-xiang Wang (Journal of Water Process Engineering, 2026)

Physiological, transcriptomic, and metabolomic insights into the sugar stress tolerance mechanisms of Clavispora lusitaniae and its fermentation potential - Ya Zhang; Siyi Liu; Runshen Zhao; Fanghang Qiu; Meiyue Han; Qiumei Zhang; Xingquan Han; Xucheng Zhu; Akhtiar Ali; Weiwei Li; Xiuting Li; Baoguo Sun (International Journal of Food Microbiology, 2026)

Dopamine-coated LTO particles immobilized in PVA with directional dendritic channels for fast and selective lithium capture from salt-lake brines - Xunshuang Zhang; Yiming Hua; Mengyu Xie; Yihan Guo; Shilei Zhu; Yu He; Junxiang Wu; Shusen Chen; Zhou Song; Ya Nan Ye; Liangbin Li (Desalination, 2026)

Numerical Investigation of Time-Dependent Deformation and Fracture Evolution in Flawed Sandstone - Teng-Fei Fu; Zhu-Guang Wang; Bi-Bi Qiao; Ya-Tao Li; Tao Ding; Chong-Feng Chen (Geotechnical and Geological Engineering, 2026)

First record of Fraxinoxylon (Oleaceae) from the Miocene of Sihong, Jiangsu Province, China, and its palaeogeographic implication - Yanbin Zhu; Ya Li; Xiaohua Zhou; Yanfeng Song; Kai Liu; Ren Jiang; Yeming Cheng (Review of Palaeobotany and Palynology, 2026)

Asymmetric Co-O-La coordination achieves biocompatible and selective generation of high-valent cobalt-oxo species for boosting water purification - Qin-Chen Li; Hai-Yan Zhu; Yi-Jun Zhang; Biao Chen; Yong-Sheng Tan; Ya-Meng Dong; Qi-Nian Wang; Wei-Kang Wang; Dong-Hua Xie; Xing Zhang (Journal of Hazardous Materials, 2026)

Environmental cadmium drives placental senescence and fetal growth restriction via activating CLPP-dependent mitochondrial stress - Rui Pan; Jin Zhang; Lan-Lan Wu; Cheng-Fang Sun; Xin-Xin Zhang; Yu-Xi Wu; Xu-Ai Yin; Ye-Xin Luo; Si-Ting Liu; Zi-Jian Bao; Wei Chang; Ling-Li Zhao; et al. (Journal of Hazardous Materials, 2026)

Target-oriented molecularly imprinted polymers enable rapid ambient ionization mass spectrometric analysis of trace tetrachlorobisphenol a in environmental samples - Ya Jiao; Shuo Gao; Xiaoxuan Han; Yong Tian; Xiaoxu Huo; Jianwei Zhao; Xiaofeng Dong; Chunguang Liu; Weiliang Wang; Guifen Zhu; Xuwei Chen; Ming-Li Chen (Journal of Hazardous Materials, 2026)

Antagonistic modulation of myosin conformational dynamics by sanshool and smoke-derived aldehydes: A molecular basis for heterocyclic amine control in thermal processing - Hongyu Deng; Jie Jia; Lihui Feng; Siwei Xiong; Hemei Yuan; Zhiyuan Fang; Qiulan Li; Shengjie Duan; Hongkang Zhu; Ya Wang; Jun Sheng; Yanping Huang; et al. (Food Chemistry, 2026)

DNA tripod-engineered signal-switchable electrochemical platform for detection of Pb2+ and Hg2+ in food samples - Mengjie Chen; Yifan Yan; Huimin Li; Ya Zhou; Liping Zhu (Food Control, 2026)

From an apposition-like stage to a superposition eye: developmental assembly of the nocturnal visual system in the diamondback moth Plutella xylostella - Ya-Fei Li; Yun-Zhu Huo; Tian Gao; Qing-Xiao Chen (Arthropod Structure & Development, 2026)

Hepatic Sirt2-PARP1-HMGB1 axis promotes exercise-mediated amelioration of MASH in mice - Shan Li; Wang-Jing Mu; Zi-Ang Zhao; Wan-Qiu Peng; Jie-Ying Zhu; Ruo-Ying Li; Lin-Jing Yan; Yang Li; Hong-Yang Luo; Min Chen; Meng-Ting Yin; Xin Li; et al. (Science China Life Sciences, 2026)

Microglial tunneling nanotubes: an intercellular transfer facilitating mitochondrial dysfunction and neuroinflammation in experimental cerebral malaria - Yan Shen; Yi Wang; Chao Yang; Jun Wang; Yuxiao Huang; Qinghao Zhu; Ganze Li; Tong Li; Jiayi Sun; Jie Ren; Xiaolin Chen; Shuhan Xing; et al. (Apoptosis, 2026)

Genome-Wide Identification of 33 Drought-Responsive P450 Genes in Sorghum Bicolor and Analyses of their Tissue-Specific Expression Under Abiotic Stress Conditions - Senjie Fu; Junxia Li; Na Qin; Ya Jing; Cancan Zhu; Shutao Dai; Chengyang Zhang; Chunyi Wang (Tropical Plant Biology, 2026)

Cerebellar Contributions to Cognitive Affective Function and Postural Tremor in Neurological Wilson’s Disease - Ping Jin; Dong-xu Yin; Yu-xie Huang; Zi-wen Li; Xin-feng Ma; Kang Lin; Ya-yun Xu; Wei-ming Gao; Qun-rong Ye; Yong-zhu Han; Gong-qiang Wang (The Cerebellum, 2026)

Soil texture modulates the impact of biodegradable microplastics on N2O emissions in agroecosystems - Ya Li; Fengxiao Zhu; Zhuyao Hua; Xiaomei Wang; Sha Chang; Changyin Zhu; Shiyin Li; Huan He; Cheng Gu (Journal of Hazardous Materials, 2026)

Freeze-casting polyamidoxime-based membrane adsorbents with synergistically enhanced mechanical properties and adsorption performance for uranium extraction from seawater - Yu He; Yanran Lu; Beibei Kang; Junxiang Wu; Xunshuang Zhang; Shilei Zhu; Zizhou Xu; Shusen Chen; Zhou Song; Ya Nan Ye; Liangbin Li (Journal of Environmental Chemical Engineering, 2026)

Multi-SsuD systems contribute to high-efficiency biodegradation of 6:2 fluorotelomer sulfonate in wastewater - Ya Bian; Shuxin Su; Yalin Yin; Yue Yang; Hengchao Zhu; Jingjing Zhang; Jingjing Liu; Lei Yao; Jingbo Gong; Jiabin Li; Yijia Wang; Wei Wang (Journal of Environmental Sciences, 2026)

Significant Mg isotope disequilibrium during crustal anatexis: Implications for heterogeneous Mg isotopic compositions in the continental crust - Er-Lin Zhu; Qiong-Xia Xia; Zhao-Ya Li; Hao-Hong Shu (Geochimica et Cosmochimica Acta, 2026)

Structure-guided discovery of neutralizing epitopes enables rational design of a multi-epitope nanoparticle vaccine against SVCV - Yu-Ya Li; Liang Zhao; Xue-Feng Wei; Xiao-Hang Ren; Jun-Yao Xia; Zhao Zhao; Bin Zhu (Fish & Shellfish Immunology, 2026)

In-situ radical polymerization for solid polymer electrolytes in lithium-ion batteries: a comprehensive review - Yong Luo; Churu Zhang; Ya Liao; Zhitian Ding; Defu Li; Lufa Zhu; Hao Luo; Beiyuan Liu; Jiali Guo; Xiaoli Peng; Shipai Song; Yong Xiang; et al. (Chemical Engineering Journal, 2026)

Hematopoiesis could be improved by correcting aberrant bone marrow macrophages polarization in aplastic anemia patients - Chen-Yuan Li; Dan-Dan Chen; Xin-Yan Zhang; Shu-Qian Tang; Meng-Zhu Shen; Ya-Ting Yu; Zhi-Wei Zhang; Zheng-Li Xu; Yuan-Yuan Zhang; Jin-Song Jia; Lan-Ping Xu; Yu Wang; et al. (Science China Life Sciences, 2026)

First report of Neopestalotiopsis iberica causing needle blight on Pinus massoniana - Kai-Yue Lü; Si-Yi Zhang; Yu Wan; Si Li; Jun-Ya Xie; De-Wei Li; Li-Hua Zhu (Crop Protection, 2026)

Text mining and machine learning based health risk prediction for soil polycyclic aromatic hydrocarbons at typical coal-fired industrial sites in china - Lu Han; Hanyuan Gu; Mengfang Chen; Zhanfei He; Yufei Jia; Yudong Feng; Jing Li; Ya Zhu; Ye zou (Journal of Hazardous Materials, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

Microglial membrane camouflaged biomimetic nanoformulation synergizing photothermal therapy and chemotherapy in glioblastoma - Ya Wang; Shuai Wu; Yunfan Li; Yuxin Huang; Kaiwen Bao; Ruyi Li; Renzheng Huan; Yuan Zhong; Li Zhu; Jianshu Li; Wei Wu; Haifeng Yang (Chemical Engineering Journal, 2026)

An AcMYB10-AcF3GT1/GST1 module restricts anthocyanin synthesis in the fruit flesh of kiwifruit - Xiao-tian Li; Zhi-xia Huang; Yu-xiao Zhai; Ya-ting Guo; Yi-tong Liu; Yan Zhang; Zhu Xie; Andrew C. Allan; Xue-ren Yin; Wen-qiu Wang (Plant Cell Reports, 2026)

Preparation of cancer cell membrane-coated Gambogic acid-loaded pH-sensitive liposomes to enhance targeted anti-hepatocellular carcinoma effect - Yi-Feng Zhang; Kun Chen; Yu-Qing Zhu; Lin Liu; Xiang-Tao Kong; Yan Dai; Xiu-Juan Fu; Ya-Ling Li; Ming-Hua Liu; Dan Zhang (Drug Delivery and Translational Research, 2026)

Contrasting effects of microplastics on N2O emission and denitrifiers in two agricultural soils - Fengxiao Zhu; Aoyu Zhou; Yuqing Ding; Haojie Wang; Sha Chang; Ya Li; Huan He (Applied Soil Ecology, 2026)

The unique biogenesis pathway of extracellular vesicles in Hirudo nipponia salivary gland cells - Ya-Li Zhu; Meng-Xiang Jia; Ru-Yu Qu; Qian Li; Xia Qiu; Wen-Chen Zhao; Yuan-Yuan Luo (Tissue and Cell, 2026)

Metamifop-induced human breast cancer cells proliferation: Revealing a proliferation mechanism distinct from 17β-estradiol - Jingjing Wu; Ya Zhou; Yu Wang; Junqi Zhu; Lu Lin; Huihua Tan; Shiling Liu; Yahui Li; Feng Zhao (Pesticide Biochemistry and Physiology, 2026)

The impact of freeze-thaw cycles on soil microbial biomass carbon and microbial community – A case study of northeastern brown soil in China - Ying Zhang; Yinghua Li; Fei Su; Chaoqun Zhu; Ya’nan Shan (Journal of Environmental Chemical Engineering, 2026)

Inhibition of ferroptosis improves mitochondrial function and color stability in postmortem beef: Associations with the NRF2/SLC7A11/PRDX6 pathway - Cai-Yun Li; Fang-Fang Lu; Li-Hua Zhu; Ya-Ning Qu; Yu-Bin Zhang (Food Bioscience, 2026)

Slow-release fertilizers applied in conjunction with manure enhanced soil quality and rice grain yield by regulating labile nutrient pools, soil enzyme activities, and soil structure - Qing Shan Xu; Yu Lian Yan; Hang Feng Wang; Shang Pan Li; Chun Xin Chi; Ya Li Kong; Wen Hao Tian; Xiao Chuang Cao; Lian Feng Zhu; Qiao Ling Li; Jing Wang Li; Jun Hua Zhang; et al. (Field Crops Research, 2026)

School greenspace and myopia incidence and burden in Chinese children and adolescents: The Guangzhou children and adolescents cohort study - Xiao-Qi Zhu; Yi Sun; Rong Lin; Ya-Na Luo; Jia-Xin Li; Yi-Dan Zhang; Michael S. Bloom; Matthew H.E.M. Browning; Sam SS. Lau; Shu-Jun Fan; Zhi-Qi Li; Ming-Deng Xiang; et al. (Environmental Research, 2026)

Histomorphological analysis of the relationship between Helicobacter pylori infection of the gastric mucosa and host immunity strength - Yang-kun Wang; Quan-wei Guo; Hai-ying He; Ying-ying Li; Chao-ya Zhu; Ping Li; Bo Jiang; Su-nan Wang; Si-liang Xu (Journal of Molecular Histology, 2026)

Phosphorus release from sediments of a drinking water reservoir under the influence of extreme water-level drawdowns - Ya Zhu; Yiping Li; Yu Chen; Can Wang; Ronghui Li; Eyram Norgbey; Yue Pan; Yaning Wang (Journal of Environmental Sciences, 2026)

Design of dual LSPR effect Ag/W18O49/PMoV heterojunction with enriched hot electron concentration at the active site for promoted photocatalytic N2 reduction - Libo Wang; Yanyu Wang; Yitong Wang; Qiguo Zhu; Na Wang; Ya Wang; Jingyao Li; Gang Liu; Zhenhua Hou (Fuel, 2026)

Enzymatic routes to initiator-based functional biodegradable polyesters - Yu Zhang; Ya Cai; Yihuan Liu; Li Xi; Xin Hu; Kai Guo; Ning Zhu (Chemical Engineering Journal, 2026)

On-deck condition and mortality of Indo-Pacific Sailfish (Istiophorus platypterus) in Indian Ocean tuna longline fisheries - Na Zhang; Wei Tang; Jie Cao; Ya’nan Li; Jiangfeng Zhu; Jiaqi Wang; Xuefang Wang (Acta Oceanologica Sinica, 2026)

Evaluation of synthetic peptide vaccines based on phage display technology for grass carp reovirus - Zhu-Yang Deng; Yu-Ya Li; Yong-Qi Liu; Le-Yang Chen; Zhao Zhao; Bin Zhu (Aquaculture, 2026)

Valorization and detoxification of MSWI fly ash via carbonation-ultrasonication for a low-chlorine, high-calcium, and low-toxicity derivative - Xuyang He; Dingyuan Zhang; Jincheng Wang; Weihua Li; Xue Li; Yingjie Sun; Qingjian Zhang; Ying Zhu; Rongxing Bian; Weichen Xu; Xuexin Fu; Ya-nan Wang; et al. (Journal of Cleaner Production, 2026)

Surface-confined primer exchange reaction enables label-free electrochemical detection of acetamiprid in agricultural products and soils - Huimin Li; Ya Zhou; Li Yang; Yao Gao; Liping Zhu (Analytica Chimica Acta, 2026)

Genetic origins and climate‐induced erosion in economically important Asian walnuts - Peng‐Zhen Fan; Guang‐Fu Zhu; Moses C. Wambulwa; Richard I. Milne; Zeng‐Yuan Wu; Ya‐Huang Luo; Robabeh Shahi Shavvon; Alistair S. Jump; Debabrata Maity; Lian‐Ming Gao; Hai‐Ling Qi; Hong‐Yu Wu; et al. (Conservation Biology, 2026)
The global climate is undergoing unprecedented changes, posing significant threats to species persistence. However, the spatiotemporal impacts on genetic diversity remain poorly understood, hindering species conservation and management. Walnuts, generally referred to as Juglans regia and J. sigillata , are economically vital in Asia, but little is known about their genetic origins and how the species will be affected by future climate change. Using 31 microsatellites, we genotyped 5282 individuals from 233 populations of walnuts in Asia. We assessed genetic diversity patterns and demographic history and investigated potential future genetic erosion risks. Genetic diversity of walnuts was high in the Himalaya and Hengduan Mountains. The 2 species diverged during the Pleistocene (around 1.41 Ma BP), and J. regia contained 2 genetic groups (JR1 and JR2). The JR2 group had the lowest diversity and likely arrived in northern China around 9.77 ka BP, perhaps via human transport. The Western Himalaya likely served both as a glacial refugium and the center of origin for J. regia , and the Eastern Himalaya appears to have been the refugium for J. sigillata . The 2 species appear to have hybridized in the Central Himalaya and the Sichuan basin and surroundings, forming two distinct hybrid zones. Our results indicate that genetic diversity will be reduced by up to 9.03% due to range loss under future climate change and dramatic genetic structure turnover in the Himalaya and Hengduan Mountains. In situ conservation in the Himalaya is essential for safeguarding genetic diversity and adaptive potential in Asian walnuts, while ex situ preservation of genetically unique wild germplasm, coupled with its integration into breeding programs, will enhance climate resilience. The findings advance our understanding of the origin of Asian walnuts and how future climatic change may affect their genetic diversity, offering a model for conservation and breeding strategies in other tree species facing similar threats.

Trans-3-hexen-1-ol as a potential attractant for the adzuki bean weevil, Callosobruchus chinensis: Evidence from reverse chemical ecology - Zi-Qing Wang; Jin-Ze An; Qiang Liu; Wen-Wen Zhu; Raul Narciso C. Guedes; Youssef Dewer; Ya-Nan Zhang; Xiao-Ming Li (Pesticide Biochemistry and Physiology, 2026)

Multi-scale evaluation of six fused evapotranspiration products over mainland China: Accuracy, consistency and uncertainty - Dayang Wang; Dagang Wang; Shaobo Liu; Zequn Lin; Ya Huang; Xiaohang Ma; Mengjiao Wu; Yanyu Ma; Jialu Zhu; B. Larry Li (Journal of Hydrology, 2026)

Target Fibroblast-B cell crosstalk via MIF signaling drives pathogenic B cell differentiation and joint damage in knee osteoarthritis - Bizhi Tu; Zheng Zhu; Yan Li; Zhengming Zhu; Shijie Wang; Peizhi Lu; Ya Li; Shuo Yang; Dingtao Hu; Run Fang; Rende Ning (Inflammation Research, 2025)

Healthy diet and slower biological aging as protective factors against microvascular complications in type 2 diabetes - Han Zhou; Shuai Ben; Qian Ma; RuiKang Yang; Jiao Xia; XiongYi Yang; Jing Li; JunYa Zhu; Qian Liu; Ya Zhao; Na Li; Kun Liu; et al. (GeroScience, 2025)

Corrigendum to “Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells” [Vet. Microbiol. 310 (2025) 110723] - Kui Xu; Yu-Ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

1-NP hijacks endocrine-metabolic checkpoints and disrupts testicular steroidogenesis by suppressing the cAMP-PKA-CREB-HMGCR axis - Xin-xin Zhu; Wei-wei Zhang; Ming-yue Hao; Zheng-ya Chen; Bai-fan Wan; Ming-hui Niu; Xiu-liang Li; Jian-hua Wei; Su-ya Liu; Shuang-ling Mi; Hua Wang; De-xiang Xu; et al. (Toxicology Letters, 2025)

Recombinant GnRH6-kisspeptin-CRM197 vaccine inhibits reproductive function in male rats and dogs - Yanyun Zhu; Mengxian Li; Xiangyang Jiang; Dongyuan Fu; Zhihao Pan; Zhuoya Wu; Kejian Han; Ya Liu; Yunsheng Li; Tong Yu; Kaiyuan Ji; Mengling Peng; et al. (The Veterinary Journal, 2025)

Bioactive sesquiterpene lactones with cytotoxic activity from Youngia japonica - Hao Gong; Kuan Lin; Lei Zhang; Yi Huang; Li-Juan Hu; Xiao-Ya Liu; Hao Ming; Si-Qi Wang; Qing-Qin He; Xian-Sheng Ye; Shu-Xiu Zhu (Phytochemistry Letters, 2025)

Effect of freezing-induced pectin degradation on the texture stability of strawberry - Ya Wang; Xuehui Cao; Qianyu Li; Rui Nian; Kaiyan You; Jingkai Su; Xuefeng Xiong; Danshi Zhu (Food Chemistry, 2025)

Engineering fast-response thermal control for dynamic gene expression design in Halomonas - Jian-Lian Wu; Ya-Ge Xiao; Bao-Wen Liu; Ling-Fan Tian; Ling-Fei Tian; Yu-Xi Li; Jia-Wen Peng; Hai-Fan Zhu; You-Yang Wang; Zhe-Yi Kuang; Jiang-Jie Tian; Shuai Zheng; et al. (Chemical Engineering Journal, 2025)

A facile and universal ligand exchange strategy enables sequential surface functionalization of quantum dots for high quality in vivo imaging - Xue-Hui Shi; Zhendong Zhu; Changlin Shen; Ya Li; Zhuang Qian; Yonghao Wu; Huifeng Chen; Qing-Qing Ye; Chaojie Hu; Yifan Song; Lei Wang; Zhimou Yang; et al. (Chemical Engineering Journal, 2025)

The critical role of mitophagy in cell senescence-mediated pulmonary fibrosis and potential therapeutic strategies - Xing-Yi Chen; Dong-Mei Wang; Ya Zhou; Li Liu; Tao Zhu; Zhao Ran; Mei-Hong Lu; Ben-Rong Mu (Molecular Biology Reports, 2025)

Exploring the low‐carbon development model for a hazardous waste treatment park from a life cycle assessment perspective - Chenqi Gao; Yating Niu; Xinran Du; Runze Zhu; Rongxing Bian; Ya'nan Wang; Yingjie Sun; Weihua Li; Qingjian Zhang; Huilai Chen (Journal of Industrial Ecology, 2025)
China is actively committed to mitigating carbon emissions through its “Dual Carbon” and “Zero‐Waste Cities” strategies. Hazardous waste (HW) treatment, a significant source of greenhouse gas (GHG) emissions, plays a crucial role in achieving carbon reduction targets. This study systematically assessed the carbon emissions and low‐carbon pathways of a representative multi‐HW treatment park in Qingdao using life cycle assessment and life cycle cost methodologies. In 2020, the total net GHG emissions of the HW park were 49,669.3 t CO 2 ‐eq, with an average emission intensity of 1181.1 kg CO 2 ‐eq per tonne of HW. Among the various treatment systems, medical waste (MW) incineration exhibited the highest GHG emission intensity (1377.6 kg CO 2 ‐eq/t MW), followed by industrial hazardous waste (IHW) incineration (1076.4 kg CO 2 ‐eq/t IHW), fly ash/slag treatment (9.7 kg CO 2 ‐eq/t HW), and physicochemical treatment (8.5 kg CO 2 ‐eq/t HW). Three integrated low‐carbon pathways demonstrated that utilizing waste heat for heating exhibited the highest carbon mitigation potential, achieving up to −403.6 kg CO 2 ‐eq/t IHW, followed by technological improvement and resource recycling. The combined low‐carbon scenario could achieve a 49.5% reduction in total carbon emissions compared to the baseline scenario. Furthermore, economic performance improved, with treatment benefits increasing from 3431.3 RMB/t IHW to 3948.5 RMB/t IHW due to enhanced energy efficiency and resource recovery. This study provides a framework for assessing multi‐HW parks’ carbon footprints and offers strategic insights for low‐carbon, resource‐efficient waste management. The findings also support sustainable multi‐HW management and contribute to climate and decarbonization efforts.

Reservoir water-level operations to manage biogeochemical turnover - Yiping Li; Yaning Wang; Xiaodong Hu; Yue Cheng; Ya Zhu; Yuxuan Zhou; Hongzhe Pan; Ronghui Li; Muhammad Ibrahim; Carlo Gualtieri (Water Research, 2025)

Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells - Kui Xu; Yu-ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Mitochondrial dysfunction-associated cellular senescence is partially involved in bleomycin-induced pulmonary fibrosis in mice - Ya-Xin Yao; Xue Lu; Zhao Li; Hao-Yu Liao; Zhi-Bing Liu; Hui Zhao; Hua Wang; De-Xiang Xu; Zhu-Xia Tan (Toxicology and Applied Pharmacology, 2025)

A strain of mycovirus AaVV1 mediates hypovirulence of Alternaria species - Ya Rong Wang; Yi Chen; Chang Xin Li; Xiao Gang Li; Jun Zi Zhu; Jie Zhong (Pesticide Biochemistry and Physiology, 2025)

PcSRB cooperates with TLR2 and promotes phagocytosis and antimicrobial peptides expression - Meng-Ke Shan; Jing-Xin Dai; Wen-Ya Li; Jing-Ru Zhu; Gui-Wen Yang; Hui-Ting Yang (Fish & Shellfish Immunology, 2025)

Electrochemical and photoelectrochemical CO2 reduction to hydrocarbons by a copper-based molecular catalyst - Zhibing Wen; Rong Zhang; Yong Zhu; Hua Gao; Ran Zhao; Zhi Chen; Siyao Wang; Shuanglin He; Ya-Qiong Zhang; Rong-Zhen Liao; Fei Li (Chemical Engineering Journal, 2025)

Establishment of succinic acid production in recombinant Kluyveromyces marxianus enhanced by AI-guided enzyme specificity engineering and redox-controlled fermentation optimization - Du-Wen Zeng; Yi-Fan Zhu; Yuan-Hong Jiang; Ya-Hao Ding; Zhen-Zhi Wang; Kai Li; Sha Liao; Ya-Chao Fan; Lin Zhang; Yu Guang Wang; Xin-Qing Zhao (Chemical Engineering Journal, 2025)

CAR19-T/NK cell and circular aptamer–drug conjugate (ApDC) combination treatment increases immunotherapy efficacy - Ling-Qi Kong; Su-Yun Chen; Xu Cui; Ya-Hui Hu; Lian Wang; Jia-Yao Zhu; Lan-Xuan Guan; Bing-Kun Wang; Li-Ting Yang; Kai-Ming Chen; Chao-Ming Zhou (Molecular and Cellular Biochemistry, 2025)

The dietary supplementation with probiotic Bacillus cereus G1-11 improved the growth parameters, immune performances, intestinal histomorphology, and disease resistance of hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) - Ming-Qing Zhang; Zhong-Xuan Zhong; Qian-Ping Du; Wen Li; Ya-Ting Zhu; Guang-Ting Xie; Feng-Ying Yan; Jin-Lin Yang; Shui-Sheng Li; Hu Shu (Animal Feed Science and Technology, 2025)

Latest progress based on doped-TiO2 photocatalysis materials: Fabrication and applications - Xiao-Ni Qi; Ya-Qi Zhu; Hui Yuan; Zi-Xuan Xu; Hao-Ran Guo; Zhen-Liang Li (Journal of Water Process Engineering, 2025)

Proteome Profiling of Serum Reveals Pathological Mechanisms and Biomarker Candidates for Cerebral Small Vessel Disease - Yun-chao Wang; Hang-hang Zhu; Liu-Chang He; Ya-ting Yao; Lei Zhang; Xin-li Xue; Jing-yi Li; Li Zhang; Bo Song; Chang-he Shi; Yu-sheng Li; Yuan Gao; et al. (Translational Stroke Research, 2025)

Construction of LncRNA-miRNA-mRNA regulatory network in IgA nephropathy mice model by RNA-sequencing and bioinformatics analysis - Wen Jia Zheng; Tao Liu; Xiao Li Zhu; Yu Ting Zhang; Liang Bing Wei; Ya Chen Gao; Xing Xing Zhuang; Jia Rong Gao (Genes & Genomics, 2025)

GSDME-dependent astrocyte pyroptosis promotes the progression of neuroinflammation in experimental cerebral malaria - Jun Wang; Qinghao Zhu; Guodong Tong; Kangjie Yu; Jiao Liang; Yuxiao Huang; Yi Wang; Chao Yang; Tong Li; Weilu Liang; Ganze Li; Xiaoran Liu; et al. (Apoptosis, 2025)

Morphology, proteome and metabolome characterization of the sporoplasm of Ameson portunus (Microsporidia) - Ya-Li Xu; Min Zhou; Zhi-Qiang Zhu; Zhao-Zhe Xin; Jin-Yong Zhang (Journal of Invertebrate Pathology, 2025)

Heavy metals contamination in water-sediment systems of a large drinking water reservoir in southern China: Large-scale assessment and risk-based management - Yiping Li; Ya Zhu; Yu Chen; Can Wang; Guoli Zhao; Haiping Pan; Chuer Wang; Hangtong Bao; Muhammad Ibrahim; Eyram Norgbey (Journal of Cleaner Production, 2025)

Thiazole-fused thiazoliniums with ketone warheads as covalent inhibitors targeting Cys44 of SARS-CoV-2 3CLpro - Qizhen Cao; Zhaoqin Zhang; Guanghao Zhu; Sanfeng Dong; Xue Sun; Yuqing Song; Ya Zhang; Tingting Cai; Xinben Zhang; Yong Zhang; Zhijian Xu; Ruisheng Xiong; et al. (Chemico-Biological Interactions, 2025)

Two alkenyl phenol derivatives from the fungus Pestalotiopsis clavata JSQ 12 isolated from the mushroom Lanmaoa asiatica - Jing Tang; Rui Xu; Hao Ma; Shuai-Ming Zhu; Fu-Yao Luo; Xue Zhao; Ya-Shuai Kang; Yuan-Wei Gao; Yu Yang; Chang-Wei Li (Natural Product Research, 2025)

Key role of macrophyte-dominated habitats over cyanobacteria-dominated habitats in stability of microbial sulfur cycling in freshwater lakes - Rui-Ze Li; Zhi-Jie Zhu; Xing-Hao Li; Yi-Ying Jiao; Li-Ya Zhao; Zhao-Hua Li; Mo Chen (Environmental Research, 2025)

Leaf and Root Traits Show Contrasting Resource Exploitation Strategies, but Converge Along Elevation in the Hengduan Mountain Forests - Jie Song; Sebastian Seibold; Liang‐Liang Ma; Jia‐Yun Zou; Jie Liu; Ming‐Shu Zhu; Wei Zheng; Zhi‐Qiong Mo; Sheng‐Ping Ming; Jin Li; Kun Xu; De‐Zhu Li; et al. (Journal of Biogeography, 2025)
Aim The variations of leaf and root traits in communities are associated with above‐ and below‐ground resource exploitation strategies and are used to infer community assembly processes along environmental gradients. However, little is known about variations in leaf and root traits and their drivers along elevations in mountain forests. Location Yulong Mountain, southeastern Hengduan Mountains, Southwest China. Taxon Seed plants. Methods We measured six leaf traits and seven root traits across 47 woody species and collected environmental variables from forest plots along a 1200 m elevational gradient. We employed linear mixed models to examine how resource exploitation strategies (community‐weighted mean, CWM) and functional diversity (standardised effect size of RaoQ, SES.RaoQ) associated with leaf and root traits varied along elevations. Furthermore, we determined the relative effects of environmental variables on these metrics. Results We observed that the resource exploitation strategy of leaves shifted from an acquisitive to a conservative strategy (higher leaf carbon concentration) with increasing elevation. Conversely, root trait variation exhibited an opposite trend, shifting from a conservative to an acquisitive strategy (higher root branching intensity but lower root diameter and root tissue density) along elevations, potentially influenced by mycorrhizal interactions. We detected functional convergence for leaf and root traits across elevations, with a greater degree of functional convergence at high elevations. Leaf trait convergence was closely linked to soil nitrogen conditions, whereas root trait convergence was associated with soil organic carbon levels. Main Conclusions Our results highlight that the patterns of resource exploitation strategies along elevational gradients are decoupled for leaf and root traits, with distinct environmental factors shaping the convergence of root and leaf traits. We argue that forest communities in mountain ecosystems may modify their resource exploitation strategies and functional diversity through varying combinations of leaf and root traits to improve resilience to future global change.

Warming exacerbates the effects of pesticides on the soil collembolan gut microbiome and antibiotic resistome - Ya-Ning Wang; Tian-Gui Cai; Ying Li; Wen-Cai Dai; Da Lin; Jin-Ting Zheng; Yi-Fei Wang; Dong Zhu (Journal of Hazardous Materials, 2025)

Rapid and efficient nitrogen removal by a novel heterotrophic nitrification-aerobic denitrification bacteria Marinobacterium maritimum 5-JS in aquaculture wastewater: Performance and potential applications - Fu-Rong Wang; Shi-Yu Feng; Shuai Liang; Wei-Yu Du; Long-Qi Wang; Yu-Wei Zhang; Jia-Yu Ren; Shuang Gao; Yu-Jie Zhu; Yu-Ting Cong; Li Wang; Jing Gu; et al. (Environmental Research, 2025)

Systematic analysis of associations between obesity and memory decline - Ying Yue Huang; Wei Sen Zhang; Jiao Wang; Chao Qiang Jiang; Feng Zhu; Ya Li Jin; Kar Keung Cheng; Tai Hing Lam; Lin Xu (GeroScience, 2025)
Despite the development of numerous obesity indicators, the optimal measure associated with memory remains to be elucidated. We examined and compared these associations whilst also exploring potential interactions with education. We analysed the associations between 20 obesity indicators and memory (measured by Delayed Word Recall Test (DWRT)) in middle-aged and older participants from Guangzhou Biobank Cohort Study by linear regression and stratification analyses. We used two-sample Mendelian randomisation (2SMR) to analyse the associations of obesity with cognitive performance. Of 20 obesity indicators, 6 and 7 were associated with poorer memory function measured by baseline and follow-up DWRT; 7 and 10 with faster memory decline measured by mean annual change (MAC) and MAC rate of DWRT. Central obesity measured by waist-to-hip-to-height ratio (WHHR) z -score showed the greatest effect size, with the β s (95% CIs) being − 0.09 (− 0.11 to − 0.07), − 0.07 (− 0.09 to − 0.04), − 0.02 (− 0.03 to − 0.01) and − 0.49 (− 0.69 to − 0.29), respectively. The associations were weaker in those with higher education ( P for education-interaction from 0.008 to 0.049). In 2SMR, body mass index (BMI), waist circumference and BMI-adjusted waist-to-hip ratio were negatively associated with cognitive performance using inverse-variance weighted method, with β s (95% CIs) being − 0.11 (− 0.15 to − 0.07), − 0.07 (− 0.12 to − 0.02) and − 0.06 (− 0.09 to − 0.02), respectively. In conclusion, obesity, especially central obesity measured by WHHR, was associated with poorer memory function and faster memory decline in middle-aged and older people, with a weaker association observed amongst those with higher education. Graphical Abstract

Demethylzeylasteral inhibits osteosarcoma cell proliferation by regulating METTL17-mediated mitochondrial oxidative phosphorylation - Jingyu Cao; Haotian Zhang; Chengbo Wang; Lihua He; Ya Li; Zimeng Wang; Xianxiao Li; Faisal Aziz; Minglei Yang; Xiangzhan Zhu (Toxicology and Applied Pharmacology, 2025)

Chemical constituents from the aerial parts of Clematis peterae - Pan-Pan Yu; Meng-Ya Chen; Ya-Ru Wu; Yong-Qi Guo; Ying-Zhen Tang; Zi-Han Zhu; Yang-Yang Ma; Shi-Hui Qian; Nan Yao; Zhen-Lin Li (Biochemical Systematics and Ecology, 2025)

Activation of NR2A-Wnt-TLR2 Signaling Axis in Satellite Glial Cells of the Dorsal Root Ganglion Contributes to Neuropathic Pain Induced by Nerve Injury in Diabetic Mice - Yan-Yan Zhang; De-Xin Zhu; Mu-Yun Wang; Ya-Ting Yi; Yu-Heng Feng; Cheng Zhou; Chun-Jie Li; Fei Liu; Jie-Fei Shen (Molecular Neurobiology, 2025)

Helicobacter pylori VacA-induced gastric mucosal atrophy: a comparative analysis with other forms of atrophic gastritis - Yang-Kun Wang; Wen-Rui Chen; Ling-Yan Lu; Ying-Ying Li; Rui-Kun Qiu; Chao-Ya Zhu; Fa-Shun Zhang; Su-Nan Wang; Si-Liang Xu (Journal of Molecular Histology, 2025)

Epidemiological and clinical profiles of respiratory syncytial virus infections in hospitalized children: a retrospective cohort study utilizing targeted next-generation sequencing - Chunyun Fu; Jialing Ruan; Lishai Mo; Jiangyang Zhao; Junming Lu; Ya Huang; Xuehua Hu; Qiang Huang; Yanhua Feng; Wenting Tang; Ning Zhu; Cuihong Lu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Oligo-residual disease in metastatic ALK-positive NSCLC treated with alectinib - Xi Yang; Xiao Chu; Ruiting Ye; Jianjiao Ni; Ya Zeng; Yue Zhou; Qing Xia; Shengping Wang; Qiao Li; Shuai Liu; Zhengfei Zhu; Li Chu (Clinical & Experimental Metastasis, 2025)

Rigidity and resilience framework-based health diagnosis of mountain forest ecosystems: A case study of Yiliang County in Yunnan Province - Li Zihui; Zhu Kangwen; Ba Yong; Zhang Ya; Yang Wantao; Wang Jie; Chen Weizhi; Dong Chunfeng; Qian Kun; Zhou Kaixuan (Journal of Cleaner Production, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

A new species of Pseudotsuga (Pinaceae) from the lower Miocene of Lesvos, Greece, and its palaeogeographical and palaeoclimatic implications - Yan-Bin Zhu; Ya Li; Jian-Ping Zhang; Yong-Dong Wang; Nikolaos Zouros (Palaeoworld, 2025)

Enhancing nitrogen removal performance of anammox granular sludge with ascorbic acid at low temperatures - Meng-Jia Zhu; Song-Ya Li; Li-Li Qiao; You-Peng Chen; Jin-Song Guo; Shao-Yang Liu; Peng Yan (Journal of Environmental Management, 2025)

Structural characterization of biohumic acid from Hongshaquan lignite degraded by Bacillus sp. XK1 and its application in the Brassica chinensis L. Growth - Chen Shi; Ya-Kun Wang; Long Yan; Yu-Hong Kang; Guang-Hui Liu; Yong Gao; Jin-Jun Bai; Yan-Jun Li; Ai-Min Wang; Ya-Nan Zhu; Xian-Yong Wei (Fuel, 2025)

Widely targeted metabolomics analysis reveals dynamic changes in metabolites of 'Hass' avocado during postharvest ripening period - Ying Xin; Na Li; Hong-Tao Zhu; Ya-Zhi Li; Han-Zhang Xiang; Jia-Huan Shang; Man Zhang; Ying-Jun Zhang (Food Chemistry, 2025)

Active immunization with a novel recombinant GnRH vaccine inhibits reproductive function in male goats - Moyan Di; Xinbao Gong; Yanyun Zhu; Shibao Guo; Zhihao Pan; Mengxian Li; Zhuoya Wu; Wei Zhang; Xuelan Liu; Ya Liu; Yunsheng Li; Jian Li; et al. (Domestic Animal Endocrinology, 2025)

Correction to: Deep plastid phylogeographic divergence of beaked hickory (Carya sinensis) calls for transboundary conservation in a biodiversity hotspot - Xiao-Yu Song; Moses C. Wambulwa; Richard Milne; Winnie W. Mambo; Zeng-Yuan Wu; Zhong-Hu Li; Ya-Huang Luo; Dinh Duy Vu; Jie Cai; Guang-Fu Zhu; Zhi-Peng Li; Lei Cai; et al. (Tree Genetics & Genomes, 2025)

Histaminergic Innervation of the Ventral Anterior Thalamic Nucleus Alleviates Motor Deficits in a 6-OHDA-Induced Rat Model of Parkinson’s Disease - Han-Ting Xu; Xiao-Ya Xi; Shuang Zhou; Yun-Yong Xie; Zhi-San Cui; Bei-Bei Zhang; Shu-Tao Xie; Hong-Zhao Li; Qi-Peng Zhang; Yang Pan; Xiao-Yang Zhang; Jing-Ning Zhu (Neuroscience Bulletin, 2025)
The ventral anterior (VA) nucleus of the thalamus is a major target of the basal ganglia and is closely associated with the pathogenesis of Parkinson’s disease (PD). Notably, the VA receives direct innervation from the hypothalamic histaminergic system. However, its role in PD remains unknown. Here, we assessed the contribution of histamine to VA neuronal activity and PD motor deficits. Functional magnetic resonance imaging showed reduced VA activity in PD patients. Optogenetic activation of VA neurons or histaminergic afferents significantly alleviated motor deficits in 6-OHDA-induced PD rats. Furthermore, histamine excited VA neurons via H1 and H2 receptors and their coupled hyperpolarization-activated cyclic nucleotide-gated channels, inward-rectifier K + channels, or Ca 2+ -activated K + channels. These results demonstrate that histaminergic afferents actively compensate for Parkinsonian motor deficits by biasing VA activity. These findings suggest that targeting VA histamine receptors and downstream ion channels may be a potential therapeutic strategy for PD motor dysfunction.

Integrating three-primary-color and white long-lasting afterglows in triphenylene-doped polymers for time/space-resolved applications - Qian Wang; Xiao-Lei Xu; Meng-Yuan Zhu; Ya-Ping Du; Yu-Juan Ma; Jin-Hua Li; Guo-Ming Wang (Chemical Engineering Journal, 2025)

Incorporating Genetic Diversity to Optimize the Plant Conservation Network in the Third Pole - Moses C. Wambulwa; Guang‐Fu Zhu; Ya‐Huang Luo; Zeng‐Yuan Wu; Jim Provan; Marc W. Cadotte; Alistair S. Jump; Francis N. Wachira; Lian‐Ming Gao; Ting‐Shuang Yi; Jie Cai; Hong Wang; et al. (Global Change Biology, 2025)
Climate change poses a significant threat to the survival of many species. Although protected areas can slow down biodiversity loss, they often lack systematic planning and do not integrate genetic diversity. Genetic diversity is a key prerequisite for species survival and the ability to tolerate new conditions. Using population genetic and distribution data from 96 plant species in the Third Pole (encompassing the Tibetan Plateau and adjacent mountains), we mapped patterns of genetic diversity, projected climate‐driven range dynamics and future genetic erosion, and designed an optimal conservation framework for the region. We identified several patches of high haplotype diversity ( H D ), with a relatively high number of haplotypes in southeastern Third Pole. Regression models revealed that climate and topography have interacted to shape patterns of genetic diversity, with latitude and precipitation being the best predictors for H D of cpDNA and nrDNA, respectively. Ecological niche modeling predicted an approximate 43 km northwestward and 86 m upward shift in suitable habitats under future climate scenarios, likely leading to a significant loss of up to 13.19% and 15.49% of cpDNA and nrDNA genetic diversity, respectively. Alarmingly, 71.20% of the newly identified conservation priority areas fall outside of the existing protected areas and planned National Park Clusters. Therefore, we recommend expanding the network by 2.02 × 10 5 km 2 (5.91%) in the Third Pole, increasing the total conserved area to 1.36 × 10 6 km 2 (39.93%) to effectively preserve the evolutionary potential of plants. This study represents an innovative attempt to incorporate genetic diversity into biodiversity conservation efforts.

Therapeutic Potential of TUBB6 Inhibition for Hematoma Reduction, Microtubule Stabilization, and Neurological Recovery in an In Vivo Model of Intracerebral Hemorrhage - Jun-Yao Huang; Qiang Ma; Ya-Jie Qi; Zhi-Yao Wang; Xiao-Guang Liu; Yi-Ming Zhu; Yu-Ping Li (NeuroMolecular Medicine, 2025)

Unveiling the metabolic heterogeneity and formation mechanism in Chinese typical Daqu based on Qu-omics - Yu Mu; Shangjie Yao; Ying Huang; Zhiyu Zhu; Dong Li; Ya Song; Zehuan Liu; Chunlin Zhang; Shirui Yu (Food Research International, 2025)

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

Corrigendum to “Platelet-rich plasma/chitosan/chondroitin sulfate immunomodulatory hydrogel co-networks for diabetic wound repair: Functions and molecular mechanisms” [Chem. Eng. J. 491 (2024) 152138] - Zi-Lin Wang; Lin-Yue Li; Hong-Jie Liu; Ya-Ling Fan; Yu-Xue Shen; Fei Song; Li-Li Zhu (Chemical Engineering Journal, 2025)

Innovative coupling pathway for second- and third-generation biomass: Efficient L-lactate synthesis from xylose and C1 compounds - Ya Wu; Gen Lu; Ruiqi Zeng; Zeyang Li; Xin Xu; Yifan Gui; Chonghao Guo; Lizhen Deng; Yutong Bie; Derui Zhang; Yuxin He; Yuyang He; et al. (Chemical Engineering Journal, 2025)

Programmed micro-nano hierarchical microspheres for the regulation of gut immunity - Xiangyu Wei; Peipei Xi; Mei Yang; Ya Wen; Minjie Chen; Li Wang; Jianwei Zhu; Yujuan Zhu; Yile Ren; Zhifeng Gu (Chemical Engineering Journal, 2025)

Do post-failure landslides become stable? - Haijun Qiu; Yijun Li; Yaru Zhu; Bingfeng Ye; Dongdong Yang; Ya Liu; Yingdong Wei (CATENA, 2025)

Membrane transport engineering for efficient yeast biomanufacturing - Xin-Yue Li; Ming-Hai Zhou; Du-Wen Zeng; Yi-Fan Zhu; Feng-Li Zhang; Sha Liao; Ya-Chao Fan; Xin-Qing Zhao; Lin Zhang; Feng-Wu Bai (Bioresource Technology, 2025)

High glucose induces renal tubular epithelial cell senescence by inhibiting autophagic flux - Ying Zhang; Yu Zhao; Yu-Qiu Liu; Ya-Ping Fang; Li Sun; Shan-Zhai Wei; Xiao-Dong Zhu; Xiao-Liang Zhang (Human Cell, 2025)

NAGK regulates the onset of puberty in female mice - Wei Zhang; Ping Qin; Mengxian Li; Zhihao Pan; Zhuoya Wu; Yanyun Zhu; Ya Liu; Yunsheng Li; Fugui Fang (Theriogenology, 2025)

Prospective LCA towards achieving carbon neutrality goals: Framework application and challenges - Ya-Xi Fang; Pei-Ze Wu; Sha Chen; Yu Li; Shu-Fen Cui; Jin-Xing Zhu; Hai-Zhou Cao; Ke-Jun Jiang; Ling Zhong (Environmental Impact Assessment Review, 2025)

Study on Mechanism of Water and Mud Inrush in Deep-Buried Large-Section Tunnel Crossing Water-Rich Fault Fracture Zone - Zu-liang Zhong; Zhuo Shen; Hong-yan Qiao; Ya-peng Li; Kai-xin Zhu (Rock Mechanics and Rock Engineering, 2025)

Construction of label-free electrochemical aptasensor and logic circuit based on triple-stranded DNA molecular switch - Ya Zhou; Li Yang; Xuemei Zhang; Li Zhu; Xiaoli Xiong; Ting Xiao; Liping Zhu (Analytica Chimica Acta, 2025)

Characteristics of collaborative innovation network and enterprise technological innovation performance: based on the moderating effect of environmental regulation - Mingxing Li; Yue Zhu; Ya Gao; Feng Chen (Environment, Development and Sustainability, 2024)

Application of botulinum toxin A in tissue repair and regeneration - Xuan-Zhu Guo; Ya-Nan Niu; Xuan Zhou; Qiao Wei; Meng Li; Jia-Ning Xia; Yu-Qi Cui; Chao-Xin Chai; Yi-Ming Wang; Li-Ping Chen (Toxicon, 2024)

The correlation between single and mixed trace elements exposure in systemic lupus erythematosus: A case-control study - Rong-Gui Huang; Kai-Di Li; Hong Wu; Yi-Yu Wang; Ya Xu; Xue Jin; Yu-Jie Du; Yi-Yuan Wang; Jing Wang; Zhang-Wei Lu; Bao-Zhu Li (Journal of Trace Elements in Medicine and Biology, 2024)

Deep learning-assisted detection of psychoactive water pollutants using behavioral profiling of zebrafish embryos - Ya Zhu; Lan Li; Shaokui Yi; Rui Hu; Jianjun Wu; Jinqian Xu; Junguang Xu; Qinnan Zhu; Shijia Cen; Yuxuan Yuan; Da Sun; Waqas Ahmad; et al. (Journal of Hazardous Materials, 2024)

Sericin peptides alleviate dextran sulfate-induced ulcerative colitis symptoms by modulating the Th17 cell differentiation pathway in C57BL/6 mice - Hongtao Zhu; Zhi-Jing Ni; Qian Zhong; Wei Wang; Ya-Jing An; Kiran Thakur; Jian-Guo Zhang; Zhong-Li Chen; Zhao-Jun Wei (Food Bioscience, 2024)

A newly NH2-UiO-66 composite functionalized by molecularly imprinted polymer for selective and rapid removal of sulfamethoxazole - Ya Jiao; Xian Li; Guohao Cheng; Jingfan Chen; Li Wang; Yongli Liu; Guifen Zhu (Environmental Research, 2024)

Engineered multienzyme-mimicking 2D bismuthene catalytic nanotriggers enable cascade enzyodynamic-boosted and synergistic GPX4/FSP1-mediated ferroptosis amplification for cancer radiosensitization - Yipengchen Yin; Li Zhu; Tiaoyan Jiang; Rong Chai; Ya Zhang; Tianyu Li; Kai Wang; Sheng Wang; Qin Zhang (Chemical Engineering Journal, 2024)

Deep plastid phylogeographic divergence of beaked hickory (Carya sinensis) calls for transboundary conservation in a biodiversity hotspot - Xiao-Yu Song; Moses C. Wambulwa; Richard Milne; Winnie W. Mambo; Zeng-Yuan Wu; Zhong-Hu Li; Ya-Huang Luo; Dinh Duy Vu; Jie Cai; Guang-Fu Zhu; Zhi-Peng Li; Lei Cai; et al. (Tree Genetics & Genomes, 2024)

A compound heterozygous mutation of ERCC8 is responsible for a family with Cockayne syndrome - Meng-Wei Liu; Cheng-Feng Hu; Jie-Yuan Jin; Rong Xiang; Liang-liang Fan; Ya-Li Li; Lei Zhu (Molecular Biology Reports, 2024)

Cadmium causes cerebral mitochondrial dysfunction through regulating mitochondrial HSF1 - Chen-Xi Li; Milton Talukder; Ya-Ru Xu; Shi-Yong Zhu; Yu-Xiang Wang; Jin-Long Li (Environmental Pollution, 2024)

Understanding the mechanisms and potential pathways of soil carbon sequestration from the biogeochemistry perspective - Xiaojuan Feng; Guohua Dai; Ting Liu; Juan Jia; Erxiong Zhu; Chengzhu Liu; Yunpeng Zhao; Ya Wang; Enze Kang; Jun Xiao; Wei Li (Science China Earth Sciences, 2024)

Trichoderma harzianum promoting chrysanthemum cutting rooting and reshaping microbial communities in endophytic and rhizosphere environments - Ya-Jie Wu; Murad Muhammad; Yu Jiao; Xiu Chen; Hai-Long Wang; Chun-Mei Lu; Xiao-Ming Wang; Guo-Xing Zhu; Kai-Qing Liu; Yue Zhang; Zi-Chao Liu; Zhi-Xing Chen; et al. (Applied Soil Ecology, 2024)

Assessing the influence of thermal structure variation on Fe and P mobility in sediments cores using Yellow Spring Instrument, diffusive gradient technology, and HR Peeper for sustainable water quality management - Robert Bofah-Buoh; Yiping Li; Eyram Norgbey; Ya Zhu; Patrick Banahene; Linda Akosua Nuamah (Environmental Science and Pollution Research, 2024)

The first dimeric indole-diterpenoids from a marine-derived Penicillium sp. fungus and their potential for anti-obesity drugs - Hui-Fang Du; Lei Li; Ya-Hui Zhang; Xu Wang; Cheng-Yan Zhou; Hua-Jie Zhu; Charles U. Pittman; Jia-Wen Shou; Fei Cao (Marine Life Science & Technology, 2024)
Obesity has become a worldwide health problem. Seeking natural products with anti-obesity activity from lots of fungi has drawn the attention of pharmacologists. In our study, dipenipenoids A and B ( 1 and 2 ), the first dimeric indole-diterpenoids with a rare C-20–C-22′ linkage, and their monomers ( 3 and 4 ), were isolated from a marine-derived Penicillium sp. CF-06 fungus from Suaeda salsa . The absolute configurations of 1 – 3 were assigned by the calculated TDDFT ECD method. The structure of 4 was verified by a single-crystal X-ray diffraction method for the first time. Interestingly, 1 and 2 displayed significant effects on the differentiation of 3T3-L1 adipocytes by down-regulating the expression of peroxisome proliferator-activated receptor gamma (PPAR γ ) and CCAAT/enhancer binding protein alpha (C/EBP α ) proteins, while monomers 3 and 4 exhibited no activity. Molecular docking results explained the mechanism that the interaction between dimer 1 and PPAR γ was stronger than that between monomer 3 and PPAR γ . Our research could provide new insight for the discovery of anti-obesity drugs.

Nrf2 deficiency exacerbated pulmonary pyroptosis in maternal hypoxia-induced intrauterine growth restriction offspring mice - Dan Chen; Ling-yun Man; Ying-ying Wang; Wei-ying Zhu; Hui-min Zhao; Sheng-peng Li; Yan-li Zhang; Shuai-chao Li; Ya-xian Wu; Ling-Ai; Qing-feng Pang (Reproductive Toxicology, 2024)

Hierarchical classification for improving parcel-scale crop mapping using time-series Sentinel-1 data - Zhou Ya'nan; Zhu Weiwei; Feng Li; Gao Jianwei; Chen Yuehong; Zhang Xin; Luo Jiancheng (Journal of Environmental Management, 2024)

Rapid and selective removal of bisphenol S from environmental samples by surface-imprinted polymer synthesized based on metal-organic framework MIL-101(Cr) - Kaixin Zhao; Xian Li; Guohao Cheng; Lin Liu; Runan Chen; Ya Jiao; Yongli Liu; Guifen Zhu (Journal of Environmental Chemical Engineering, 2024)

A One-Nano MOF-Two-Functions Strategy Toward Self-healing, Anti-inflammatory, and Antibacterial Hydrogels for Infected Wound Repair - Ya-Ling Fan; Hong-Jie Liu; Zi-Li Wang; Zi-Lin Wang; Li-Li Zhu; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2024)

Long-term prediction method for PM2.5 concentration using edge channel graph attention network and gating closed-form continuous-time neural networks - Chen Zhang; Xiaofan Li; Hongyang Sheng; Ya Shen; Wei Xie; Xuhui Zhu (Process Safety and Environmental Protection, 2024)

Chemosensory protein 22 in Riptortus pedestris is involved in the recognition of three soybean volatiles - Nan Gu; Yu-Wen Chen; Sai Ma; Qiang Liu; Jian-Qiao Li; Shu-Han Yang; Wen-Wen Zhu; Jin-Bu Li; Xiu-Yun Zhu; Xiao-Ming Li; Ya-Nan Zhang (Pesticide Biochemistry and Physiology, 2024)

A pooled mycoviral resource in a strain of Rhizoctonia solani are regulators of fungal virulence - Ya Rong Wang; Jia En Su; Zhi Juan Yang; Jie Zhong; Xiao Gang Li; Yi Chen; Jun Zi Zhu (Pesticide Biochemistry and Physiology, 2024)

Competition between discharge reaction and side reaction for anode's lithium during internal short circuit in lithium-ion batteries - Cong-jie Wang; Yan-li Zhu; Tao Zhang; Jun Tian; Fei Gao; Yong Zhao; Xin-ya Bu; Ting Quan (Journal of Cleaner Production, 2024)

Zirconium isotope tracing of the magmatic-hydrothermal transition - Er-Lin Zhu; Qiong-Xia Xia; Shao-Bing Zhang; James Van Orman; Ren-Xu Chen; Zhao-Ya Li; Peng Gao (Geochimica et Cosmochimica Acta, 2024)

Identification of attractants for adult Spodoptera litura based on the interaction between odorant-binding protein 34 and host volatiles - Yu-Wen Chen; Hui-Hui Yang; Nan Gu; Jian-Qiao Li; Xiu-Yun Zhu; Ya-Nan Zhang (Pesticide Biochemistry and Physiology, 2024)

Effects of ultrasonic pretreatment on drying characteristics and water migration characteristics of freeze-dried strawberry - Xinyue Zhang; Ya Wang; Rui Nian; Qianyu Li; Danshi Zhu; Xuehui Cao (Food Chemistry, 2024)

Electrocatalytic nitrogen reduction to ammonia at low overpotentials based on tungsten carbide doped by non-precious metal single cobalt atoms - Ya Gao; Meng-Jiao Zhu; Xian-He Liu; Guo-Liang Dai; Yi-Wen Zhou; Ze-Da Meng; Li Luo; Tian Gan; Feng Chen; Yu-Yang Zhou; Wen-Wen Deng; Shou-Qing Liu (Chemical Engineering Journal, 2024)

Development of the near-infrared fluorescence probe for detection of ONOO− and its application in vitro and vivo - Ya-Jing Shang; Yuan-Yuan Li; Jia-Ling Hu; Yi-Ru Wang; Sheng-Tao Li; Xing-Hu Wu; Ai-Hong Zhang; Yu-Wei Tan; Ting Liang; Xiao-Bo Zhu; Yan-Fei Kang (Analytica Chimica Acta, 2024)

Shoot blight of Pinus bungeana caused by Diplodia sapinea newly reported in China - Jun-Ya Xie; Hui Li; Yu Wan; De-Wei Li; Li-Hua Zhu (Crop Protection, 2024)

Niche convergence and biogeographic history shape elevational tree community assembly in a subtropical mountain forest - Liang-Liang Ma; Sebastian Seibold; Marc W. Cadotte; Jia-Yun Zou; Jie Song; Zhi-Qiong Mo; Shao-Lin Tan; Lin-Jiang Ye; Wei Zheng; Kevin S. Burgess; Zhi-Fa Chen; De-Tuan Liu; et al. (Science of The Total Environment, 2024)

Nano‑selenium alleviates cadmium-induced blood-brain barrier destruction by restoring the Wnt7A/β-catenin pathway - Chen-Xi Li; Milton Talukder; Zhao-Yi Wang; Shi-Yong Zhu; Ya-Ru Xu; Xue-Nan Li; Jin-Long Li (Science of The Total Environment, 2024)

Carbonized polymer dots-based molecular imprinting: An adsorbent with enhanced selectivity for highly efficient recognition and removal of ceftiofur sodium from complex samples - Li Wang; Lin Liu; Runan Chen; Ya Jiao; Kaixin Zhao; Yongli Liu; Guifen Zhu (Journal of Hazardous Materials, 2024)

Evolution of physicochemical and leaching characteristics of municipal solid waste incineration fly ash in China under ultra-low emission standard - Guangyuan Yao; Rongbin Xu; Zhu Liang; Ping Li; Ya Xu; Yuqiang Liu; Can Qian; Qifei Huang (Journal of Environmental Management, 2024)

Platelet-Rich Plasma/Chitosan/Chondroitin sulfate immunomodulatory hydrogel Co-Networks for diabetic wound Repair: Functions and molecular mechanisms - Zi-Lin Wang; Lin-Yue Li; Hong-Jie Liu; Ya-Ling Fan; Yu-Xue Shen; Fei Song; Li-Li Zhu (Chemical Engineering Journal, 2024)

Confined-immigration enhances water resistance and weatherability of highly transparent coatings for cultural heritage preservation - Lin Chen; Heng Zhang; Shilei Zhu; Zhuangzhuang Li; Wenwen Yu; Fengbo Zhu; Ya Nan Ye; Qiang Zheng (Chemical Engineering Journal, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Adaptation of a prey population to increasing predation risks - Ling Pan; Han Zhu; Yan Wang; Bao-Chun Shi; Xin-Feng Cheng; Ya-Li Ge; Xian-Ling Xiang; Xin-Li Wen; Yi-Long Xi (Hydrobiologia, 2024)

3D bioprinting of DPSCs with GelMA hydrogel of various concentrations for bone regeneration - Wen Wang; Yaru Zhu; Ya Liu; Banghui Chen; Mengying Li; Changyong Yuan; Penglai Wang (Tissue and Cell, 2024)

Parent material influences soil properties to shape bacterial community assembly processes, diversity, and enzyme-related functions - Yu-Zhu Li; Xue-Lian Bao; Xue-Feng Zhu; Fang-Bo Deng; Ya-Li Yang; Yue Zhao; Hong-Tu Xie; Shi-Xin Tang; Cheng-Jun Ge; Chao Liang (Science of The Total Environment, 2024)

Anti-inflammatory activity of organic acids from the seeds of Phaseolus lunatus L. - Kun Li; Jin-hui Bian; Heng Wu; Ya-lan Wang; Yun-jia Feng; Jia Nie; Na Chen; Han Yu; Wan Li; Yu-zhu Tan; Guang-hua Lu (Phytochemistry Letters, 2024)

Genome-wide analysis of in vivo-evolved Candida auris reveals multidrug-resistance mechanisms - Xin-Fei Chen; Han Zhang; Ling-Li Liu; Li-Na Guo; Wen-Jing Liu; Ya-Li Liu; Ding-Ding Li; Ying Zhao; Ren-Yuan Zhu; Yi Li; Rong-Chen Dai; Shu-Ying Yu; et al. (Mycopathologia, 2024)

Therapeutic effects and mechanisms of isoxanthohumol on DSS-induced colitis: regulating T cell development, restoring gut microbiota, and improving metabolic disorders - Ya-Na Yang; Bing Han; Mao-Qing Zhang; Na-Nan Chai; Feng-Lin Yu; Wen-Hui Qi; Meng-Yuan Tian; Dong-Zhi Sun; Ying Huang; Qing-Xin Song; Yan Li; Mao-Cui Zhu; et al. (Inflammopharmacology, 2024)

The influence of biological sex in human skeletal muscle transcriptome during ageing - Xiaoyu Huang; Mao Chen; Ya Xiao; Fangyi Zhu; Liying Chen; Xiaoyu Tian; Li Hong (Biogerontology, 2024)

Binding properties of chemosensory protein 4 in Riptortus pedestris to aggregation pheromones - Jin-Bu Li; Qiang Liu; Sai Ma; Yue-Ying Wang; Xing-Zhou Liu; Chao-Wei Wang; Da-Jiang Wang; Zhuang-Zhuang Hu; Jia-Wen Gan; Xiu-Yun Zhu; Bao-Ping Li; Mao-Zhu Yin; et al. (Pesticide Biochemistry and Physiology, 2024)

Spatial-temporal constraints for surface soil moisture mapping using Sentinel-1 and Sentinel-2 data over agricultural regions - ZHOU Ya'nan; WANG Binyao; ZHU Weiwei; FENG Li; HE Qisheng; ZHANG Xin; WU Tianjun; YAN Na'na (Computers and Electronics in Agriculture, 2024)

Di (2-ethylhexyl) phthalate induced lipophagy-related renal ferroptosis in quail (Coturnix japonica) - Yu Zhu; Xiang-Yu Ma; Ling-Ge Cui; Ya-Ru Xu; Chen-Xi Li; Milton Talukder; Xue-Nan Li; Jin-Long Li (Science of The Total Environment, 2024)

Corrigendum to “Cross-species analysis of transcriptome emphasizes a critical role of TNF-α in mediating MAP2K7/AKT2 signaling in zearalenone-induced apoptosis” [J Hazard Mater 459 (2023) 132226] - Fa-Li Zhang; Ke-Xin Zhu; Jing-Ya Wang; Min Zhang; Jia-Mao Yan; Qing-Chun Liu; Xiao-Yuan Zhang; Jia-Chen Guo; Xuan Liu; Qi-cheng Sun; Wei Ge; Lan Li; et al. (Journal of Hazardous Materials, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Artificial infection pathway of largemouth bass LMBV and identification of resistant and susceptible individuals - Ya Zhang; Bin Gui; Zhihui Jia; Yongming Li; Lanjie Liao; Zuoyan Zhu; Yaping Wang; Rong Huang (Aquaculture, 2024)

Insights into the differential molecular response of non-germinated and germinated spores of Ameson portunus in vitro by comparative transcriptome analysis - Zhao-Zhe Xin; Zhi-Qiang Zhu; Jiu-Yang Chen; Ya-Li Xu; Xin-Tong Zhang; Jin-Yong Zhang (Journal of Invertebrate Pathology, 2024)

Thermal stratification and mixing processes response to meteorological factors in a monomictic reservoir - Yaning Wang; Yiping Li; Yue Cheng; Yu Wang; Ya Zhu; Ronghui Li; Kumud Acharya; Muhammad Ibrahim (Journal of Environmental Management, 2024)

Auxin acts upstream of nitric oxide to regulate cell wall xyloglucan and its aluminium-binding capacity in Arabidopsis thaliana - Su Li; Jie Ya Sun; Hao Yu Wang; Huai Kang Jing; Ren Fang Shen; Xiao Fang Zhu (Planta, 2024)

Heat shock induces HuR-dependent MKP-1 posttranslational regulation through the p38 MAPK signaling cascade - Xiao-juan Ma; Zhan Sun; Yi-ping Wang; Xue-ping Yao; Ting-ting Luo; Ya-li Bao; Dina Ainiwaer; Tian Zhang; Hengyi Zhu; Yan Zhang; Fei-ming Hu; Wen-yan Yu (Tissue and Cell, 2024)

Clerodane diterpenoids with in-vitro anti-neuroinflammatory activity from the tuberous root of Tinospora sagittata (Menispermaceae) - Jia-Qi Song; Kai-Cheng Yang; Xian-Zhe Fan; Li Deng; Yang-Li Zhu; Hong Zhou; Ya-Si Huang; Xiang-Qian Kong; Li-Jun Zhang; Hai-Bing Liao (Phytochemistry, 2024)

A new cyclohexenone derivative from phomopsis sp. XM-01 - Cheng-Yao Wang; Dong Gan; Chen-Zhe Li; Li Zhu; Xiao-Ran Zhang; Ya-Ni Li; Xiu-Hong Wu; Hao Zhou; Le Cai (Natural Product Research, 2024)

Potential protective effects of sodium butyrate on glycinin-induced oxidative stress, inflammatory response, and growth inhibition in Cyprinus carpio - Deng-Lai Li; Si-Ying Liu; Rui Zhu; Si-Tong Meng; Yin-Tao Wang; Zhi-Yong Yang; Liang Li; Xiao-Fang Wei; Guo-Jun Shang; Hao-Tong Wang; Zi-Hui Qu; Ya-Nan Quan; et al. (Fish Physiology and Biochemistry, 2024)

Retraction Note: Autophagy regulated by lncRNA HOTAIR contributes to the cisplatin-induced resistance in endometrial cancer cells - Meng-Yao Sun; Jian-Yong Zhu; Chun-Yan Zhang; Miao Zhang; Ya-Nan Song; Khalid Rahman; Li-Jun Zhang; Hong Zhang (Biotechnology Letters, 2024)

Anthropogenic disturbance driving population decline of a dominant tree in East Asia evergreen broadleaved forests over the last 11,000 years - Sheng‐Yuan Qin; Zheng‐Yu Zuo; Shuang‐Xiu Xu; Jie Liu; Feng‐Mao Yang; Ya‐Huang Luo; Jun‐Wei Ye; Yao Zhao; Jun Rong; Bing Liu; Peng‐Fei Ma; De‐Zhu Li (Conservation Biology, 2024)
Current biodiversity loss is generally considered to have been caused by anthropogenic disturbance, but it is unclear when anthropogenic activities began to affect biodiversity loss. One hypothesis suggests it began with the Industrial Revolution, whereas others propose that anthropogenic disturbance has been associated with biodiversity decline since the early Holocene. To test these hypotheses, we examined the unique vegetation of evergreen broadleaved forests (EBLFs) in East Asia, where humans have affected landscapes since the early Holocene. We adopted a genomic approach to infer the demographic history of a dominant tree ( Litsea elongata ) of EBLFs. We used Holocene temperature and anthropogenic disturbance factors to calculate the correlation between these variables and the historical effective population size of L. elongata with Spearman statistics and integrated the maximum‐entropy niche model to determine the impact of climate change and anthropogenic disturbance on fluctuation in its effective population size. We identified 9 well‐defined geographic clades for the populations of L. elongata . Based on the estimated historical population sizes of these clades, all the populations contracted, indicating persistent population decline over the last 11,000 years. Demographic history of L . elongata and human population change, change in cropland use, and change in irrigated rice area were significantly negatively correlated, whereas climate change in the Holocene was not correlated with demographic history. Our results support the early human impact hypothesis and provide comprehensive evidence that early anthropogenic disturbance may contribute to the current biodiversity crisis in East Asia.

Effects of operating conditions on the in situ control of sulfur-containing odors by using a novel alternative landfill cover and its transformation mechanism - Jiayi Zhang; Xiaowen Li; Aiai Qian; Xianwen Xu; Ya Lv; Xinrong Zhou; Xinrui Yang; Weiqin Zhu; Hangjun Zhang; Ying Ding (Environmental Science and Pollution Research, 2024)

Adaptive evolution in asymptomatic host confers MDR Salmonella with enhanced environmental persistence and virulence - Bing He; Ting-ting Zhu; Yin Liang; Hai-jing Wei; Zi-lei Huang; Li-jie Liang; Jia-hao Zhong; Yang Luo; Xin-lei Lian; Dong-hao Zhao; Xiao-ping Liao; Ya-hong Liu; et al. (Science of The Total Environment, 2024)

Unlocking the potential of N-acetylcysteine: Improving hepatopancreas inflammation, antioxidant capacity and health in common carp (Cyprinus carpio) via the MAPK/NF-κB/Nrf2 signalling pathway - Rui Zhu; Guo-Jun Shang; Bao-Yuan Zhang; Hao-Tong Wang; Liang Li; Xiao-fang Wei; Deng-Lai Li; Zhi-Yong Yang; Zi-Hui Qu; Ya-Nan Quan; Si-Ying Liu; Yin-Tao Wang; et al. (Fish & Shellfish Immunology, 2024)

Simultaneously tuning oxygen reduction pathway and charge transfer dynamics toward sacrificial agent-free photocatalytic H2O2 production for in-situ water disinfection - Ya-Ya Yang; Hai Guo; Da-Wei Huang; Lu Li; Hui-Yun Liu; Long Sui; Qian Wu; Jing-Jing Zhu; Lei Zhang; Cheng-Gang Niu (Chemical Engineering Journal, 2024)

A metal-phenolic network-assembled nanotrigger evokes lethal ferroptosis via self-supply loop-based cytotoxic reactions - Xinping Zhang; Yuxin Guo; Xiaoyang Liu; Shun-Yu Wu; Ya-Xuan Zhu; Shao-Zhe Wang; Qiu-Yi Duan; Ke-Fei Xu; Zi-Heng Li; Xiao-Yu Zhu; Guang-Yu Pan; Fu-Gen Wu (Chemical Engineering Journal, 2024)

Fructooligosaccharides and fructans from Platycodon grandiflorum: Structural characterization, lung-oriented guidance and targetability - Jun Liang; Wen-Fei Wang; Yi Zhang; Yan-Qun Chai; Ya-Ge Li; Si-Liang Jiang; Xin-Hua Zhu; Yu-Li Guo; Zhen Wei; Xi-Zhe Sun; Hai-Xue Kuang; Yong-Gang Xia (Carbohydrate Polymers, 2024)

Constructing an eco-friendly and ratiometric fluorescent sensor for highly efficient detection of mercury ion in environmental samples - Yongli Liu; Letian Chen; Xiaoyan Su; Li Wang; Ya Jiao; Penghui Zhou; Bin Li; Ruijuan Duan; Guifen Zhu (Environmental Science and Pollution Research, 2023)

Multiple paternally inherited chloroplast capture events associated with Taxus speciation in the Hengduan Mountains - Han-Tao Qin; Michael Mӧller; Richard Milne; Ya-Huang Luo; Guang-Fu Zhu; De-Zhu Li; Jie Liu; Lian-Ming Gao (Molecular Phylogenetics and Evolution, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Impact of Eucalyptus residue leaching on iron distribution in reservoir sediments assessed by high-resolution DGT technique - Ya Zhu; Yiping Li; Yao Wei; Eyram Norgbey; Yu Chen; Ronghui Li; Can Wang; Yu Cheng; Robert Bofah-Buoh (Environmental Science and Pollution Research, 2023)

Socioeconomic status, lifestyle and risk of incident dementia: a prospective cohort study of 276730 participants - Ya-Nan Ou; Yan-Bo Zhang; Yu-Zhu Li; Shu-Yi Huang; Wei Zhang; Yue-Ting Deng; Bang-Sheng Wu; Lan Tan; Qiang Dong; An Pan; Ren-Jie Chen; Jian-Feng Feng; et al. (GeroScience, 2023)

Monoterpenoids from the root bark of Acanthopanax gracilistylus and their inhibitory effects on neutrophil elastase, 5-lipoxygenase, andcyclooxygenase-2 in vitro - Hao-Dong Yang; Zhi-Shu Tang; Tao-Tao Xue; Huai-Li Xu; Bao-Long Hou; Ya-Ya Zhu; Zeng-Hu Su; Hong-Bo Xu (Phytochemistry, 2023)

Water network integration for industrial park based on numerical indicators - Xiao-Yan Fan; Xiao-Jie Li; Ya-Xuan Zhu; Zhi-Yong Liu; Yuan Shang (Journal of Cleaner Production, 2023)

Ångstrom-scale silver particles ameliorate collagen-induced and K/BxN-transfer arthritis in mice via the suppression of inflammation and osteoclastogenesis - Ze-Hui He; Jing-Tao Zou; Xia Chen; Jiang-Shan Gong; Ya Chen; Ling Jin; Yi-Wei Liu; Shan-Shan Rao; Hao Yin; Yi-Juan Tan; Zun Wang; Wei Du; et al. (Inflammation Research, 2023)

Rapid adaptation of a rotifer prey population to non-consumptive predation pressures - Ling Pan; Han Zhu; Yi-Long Xi; Xin-Feng Cheng; Ya-Li Ge; Xian-Ling Xiang; Xin-Li Wen (Hydrobiologia, 2023)

Valbenazine promotes body growth via growth hormone signaling during zebrafish embryonic development - Zhengkang Su; Ziru Dai; Fengqing Qin; Hai Zhang; Miaomiao Zheng; Ya Zhu; Zhiqian Tong; Weihong Song; Xi Li (Toxicology and Applied Pharmacology, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Surface characteristic driven in waste printed circuit boards flotation: Floatability mechanism of resin and glass fiber in non-metallic component - Chun-chen Nie; Si-qi Jiang; Xi-guang Li; Xian-jun Lyu; Ya-qing Zhang; Xiang-nan Zhu (Process Safety and Environmental Protection, 2023)

Cross-species analysis of transcriptome emphasizes a critical role of TNF-α in mediating MAP2K7/AKT2 signaling in zearalenone-induced apoptosis - Fa-Li Zhang; Ke-Xin Zhu; Jing-Ya Wang; Min Zhang; Jia-Mao Yan; Qing-Chun Liu; Xiao-Yuan Zhang; Jia-Chen Guo; Xuan Liu; Qi-Cheng Sun; Wei Ge; Lan Li; et al. (Journal of Hazardous Materials, 2023)

Environmentally relevant concentrations of fipronil selectively disrupt venous vessel development in zebrafish embryos/larvae - Ya Ma; Qicheng Zhu; Shili Luo; Fenghong Zhang; Lei Liu; Mengxue Zhi; Zhuyi Zhang; Xiaolian Cao; Xuelin Qiu; Xiangyu Zeng; Di Ji; Chenxin Li; et al. (Chemosphere, 2023)

Halogenated bisphenol A derivatives potently inhibit human, rat, and mouse gonadal 3β-hydroxysteroid dehydrogenases: Structure-activity relationship and in silico molecular docking analysis - Yang Yu; Mengyun Wang; Ya Chen; Chengshuang Pan; Qianjin Fei; Yang Zhu; Huitao Li; Ren-shan Ge (Toxicology Letters, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

An extracellular matrix-inspired self-healing composite hydrogel for enhanced platelet-rich plasma-mediated chronic diabetic wound treatment - Ya Zhang; Zi-Li Wang; Ze-Peng Deng; Zi-Lin Wang; Fei Song; Li-Li Zhu (Carbohydrate Polymers, 2023)

nNOS and Neurological, Neuropsychiatric Disorders: A 20-Year Story - Li-Juan Zhu; Fei Li; Dong-Ya Zhu (Neuroscience Bulletin, 2023)

Rice Straw Biochar is More Beneficial to Soil Organic Carbon Accumulation and Stabilization than Rice Straw and Rice Straw Ash - Mengru He; Ya Jiang; Yuhang Han; Wenhao Zhu; Da Meng; Cuilan Li; Hongguang Cai; Jinjing Zhang (Journal of Soil Science and Plant Nutrition, 2023)

Synthesis and anti‐parasites efficacy of coumarin derivatives against Dactylogyrus intermedius - Guang‐Lu Liu; Hui Zhang; Li‐Li Zhu; Xu‐Dong Liu; Yan‐Jie Liu; Ya‐hong Chen; Lei Liu; Yang Hu (Journal of Fish Diseases, 2023)
Dactylogyrus is one of the most common parasitic diseases in fish and causes huge losses to the aquaculture industry. With the advantages of safety, low toxicity and easy degradation, plant‐derived drugs are ideal for the creation of green aquatic ingredients. The use of plant‐derived drugs in aquaculture is limited by their low content and high processing costs, which is a challenge that can be solved by the chemical synthesis of plant‐derived drugs. Eleven new coumarin derivatives were synthesized and assessed for their anthelmintic activity in this study. Among them, the derivative 7‐((1‐tosyl‐1H‐1,2,3‐triazol‐4‐yl)methoxy)‐2H‐chromen‐2‐one (N11) has good anthelmintic activity and its mean anthelmintic efficacy against D. intermedius at a concentration of 10 μM reached 99.84%, which is even better than the anthelmintic activity of the positive control mebendazole. Further studies showed that N11 had concentration values of 3.31 and 1.94 μM for 50% maximal effect (EC 50 ) against D. intermedius at 24 and 48 h, respectively. Furthermore, scanning electron microscopy revealed that N11 caused damage to D. intermedius . What is more noteworthy is that a substantial reduction in the ATP content of the parasite was observed following in vitro and in vivo administration of N11. Moreover, it was also found that N11 was able to inhibit the horizontal transmission of D. intermedius . Furthermore, real‐time quantitative PCR analysis was utilized to determine the expression profile of genes associated with anti‐inflammatory cytokines (IL‐10 , TGF‐β and IL‐4 ) in goldfish. In all examined organs, it was observed that the expression of anti‐inflammatory cytokines increased subsequent to treatment with N11, according to the results. Thus, these results all suggest that N11 possesses good anthelmintic activity and is a potentially effective agent for the control of D. intermedius .

Pallamins A–C, ent-labdane and pallavicinin based dimers from the Chinese liverwort Pallavicinia ambigua (mitt.) stephani - Yi Li; Xiao-Bin Li; Jin-Chuan Zhou; Ze-Jun Xu; Ming-Zhu Zhu; Yan Zong; Jiao-Zhen Zhang; Jing-Jing Han; Ya-Jie Tang; Hong-Xiang Lou (Phytochemistry, 2023)

Binding properties of chemosensory protein 12 in Riptortus pedestris to aggregation pheromone (E)-2-hexenyl (Z)-3-hexenoate - Mao-Zhu Yin; Jian-Qiao Li; Qiang Liu; Sai Ma; Zhuang-Zhuang Hu; Xing-Zhou Liu; Chao-Wei Wang; Wei-Chen Yao; Xiu-Yun Zhu; Yue-Ying Wang; Jin-Bu Li; Ya-Nan Zhang (Pesticide Biochemistry and Physiology, 2023)

Improving oxidation removal of toluene in plasma coupling perovskite catalysts system by constructing Au sites on a La0.5Ce0.5CoO3-δ - Bin Zhu; Qi-Wei Li; Ye-Cheng Li; Ya-Qiang Xia; Jing-Lin Liu; A-Min Zhou; Xiao-Min Zhang (Chemical Engineering Journal, 2023)

Novel biological nitrogen removal process for the treatment of wastewater with low carbon to nitrogen ratio: A review - Kaiyao Hu; Wenxuan Li; Yaning Wang; Bo Wang; Hao Mu; Shuang Ren; Kexin Zeng; Hongjuan Zhu; Jinming Liang; Ya'e Wang; Juqiang Xiao (Journal of Water Process Engineering, 2023)

Effects of microplastics in aquatic environments on inflammatory bowel disease - Jiali Ji; Xinyue Wu; Xi Li; Ya Zhu (Environmental Research, 2023)

Long-term cadmium exposure induces chronic obstructive pulmonary disease-like lung lesions in a mouse model - Wen-Jing Wang; Kun Peng; Xue Lu; Yan-Yan Zhu; Zhao Li; Qing-Hua Qian; Ya-Xin Yao; Lin Fu; Yan Wang; Yi-Chao Huang; Hui Zhao; Hua Wang; et al. (Science of The Total Environment, 2023)

Two generations of crustal anatexis in association with two-stage exhumation of ultrahigh-pressure metamorphic rocks in the Dabie orogen - Qiong-Xia Xia; Meng Yu; Er-Lin Zhu; Ren-Xu Chen; Wan-Cai Li; Yong-Fei Zheng; Zi-Fu Zhao; Zhao-Ya Li (Lithos, 2023)

Non-thermal effects of microwave irradiation alleviates postharvest chilling injury of peach fruit by retarding phenolic accumulation and enhancing membrane stability - Ke Wang; Ge Zhu; Ya-li Li; Shu-qi Chen; Arif Rashid; Xiao-tong Wang; Xin-yu Wu (Food Chemistry, 2023)

Isolation and characterization of 46 SNP markers in Gymnocypris chilianensis - Ya Liu; Wenqiong Wu; Siyi Zhu; Yeyu Chen; Xiaoyun Wu; Jiansheng Lai; Mingjiang Song; Feiyang Li; Qiang Li (Conservation Genetics Resources, 2023)

Colonic mechanism of serum NAD+ depletion induced by DEHP during pregnancy - Yun Hong; Xia Ning; Yue-yue Liang; Xiao-lu Li; Ya Cui; Wei Wu; Yang Cai; Shuai Zhao; Meng Zhu; Tian-xiao Zhong; Hua Wang; De-xiang Xu; et al. (Science of The Total Environment, 2023)

Ligand-binding properties of chemosensory protein 1 in Callosobruchus chinensis to mung bean volatiles - Qiang Liu; Mao-Zhu Yin; Sai Ma; Nan Gu; Li-Fu Qian; Ya-Nan Zhang; Xiao-Ming Li (Pesticide Biochemistry and Physiology, 2023)

Cadmium aggravates the blood-brain barrier disruption via inhibition of the Wnt7A/β-catenin signaling axis - Chen-Xi Li; Milton Talukder; Ya-Ru Xu; Shi-Yong Zhu; Ying-Xin Zhao; Jin-Long Li (Environmental Pollution, 2023)

The effect of phthalates exposure during pregnancy on asthma in infants aged 0 to 36 months: a birth cohort study - Jian-Qing Wang; Chun-Mei Liang; Ya-Bin Hu; Xun Xia; Zhi-Juan Li; Hui Gao; Jie Sheng; Kun Huang; Su-Fang Wang; Peng Zhu; Jia-Hu Hao; Fang-Biao Tao (Environmental Geochemistry and Health, 2023)

Investigation on the concentration prediction model and personnel hazard range of LNG leakage from tankers in the tunnel - Wensheng Sun; Shigang Yang; Ya Yang; Qin Fang; Jianlu Zhu; Junhao Dai; Haoyang Li (Process Safety and Environmental Protection, 2023)

Functional differentiation of two general odorant-binding proteins to sex pheromones in Spodoptera frugiperda - Hui-Hui Yang; Shu-Peng Li; Mao-Zhu Yin; Xiu-Yun Zhu; Jin-Bu Li; Ya-Nan Zhang; Xiao-Ming Li (Pesticide Biochemistry and Physiology, 2023)

Engineering spatial locations of Pt in hierarchically porous KL zeolite by atomic layer deposition with enhanced n-heptane aromatization - Shuyuan Wang; Ya Gao; Li Wei; Mengxia Yan; Fengjiao Yi; Jianmei Wang; Luyuan Wang; Guofu liu; Angang Song; Yan Li; Feipeng Cai; Di Zhu; et al. (Fuel, 2023)

Maximizing sound absorption, thermal insulation, and mechanical strength of anisotropic pectin cryogels - Fangxin Zou; Jose Cucharero; Yujiao Dong; Pinja Kangas; Ya Zhu; Janne Kaskirinne; Girish C. Tewari; Tuomas Hänninen; Tapio Lokki; Hailong Li; Jaana Vapaavuori (Chemical Engineering Journal, 2023)

The diversity of mycorrhiza‐associated fungi and trees shapes subtropical mountain forest ecosystem functioning - Ya‐Huang Luo; Liang‐Liang Ma; Sebastian Seibold; Marc W. Cadotte; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Wei Zheng; Jia‐Yun Zou; Zhi‐Fa Chen; De‐Tuan Liu; Guang‐Fu Zhu; et al. (Journal of Biogeography, 2023)
Aim Mycorrhiza play key roles for ecosystem structure and functioning in forests. However, how different mycorrhizal types influence mountain forest biodiversity–ecosystem functioning (BEF) relationships are largely unknown. We evaluate how the diversity of distinct mycorrhiza‐associated fungi and trees shapes forest carbon storage along elevational gradients. Location Gaoligong Mountains within Hengduan Mountains, Southwest China. Taxon Seed plants and mycorrhizal fungi. Methods We used the data from 31 subtropical forest plots along elevational gradients on two aspects (east and west) of the mountain. We quantified species richness of trees and symbiotic fungi and assigned both to their mycorrhizal type (arbuscular mycorrhiza [AM], ectomycorrhiza [EcM] and ericoid mycorrhiza [ErM]). We then examined the diversity effects of mycorrhiza‐associated fungi and trees on above‐ground carbon stored in trees and organic carbon stored in soils. Results Species richness was highest for AM trees (79.5%), followed by ErM trees (13.4%) and then EcM trees (7.1%). Species richness of AM‐associated trees and fungi decreased with increasing elevation, while ErM‐associated trees and fungi showed an opposite trend. EcM‐associated diversity followed a hump‐shaped relationship with elevation. Positive relationships between diversity and above‐ground carbon were detected in all three mycorrhizal associations, but despite low species number, canopy‐dominating EcM trees comprised 64.4% of the amount of above‐ground carbon. Furthermore, community‐weighted means of height exhibited positive correlations with forest above‐ground carbon, indicating that positive selection effects occur. Soil organic carbon was positively related to EcM‐associated fungi diversity, above‐ground carbon mass and soil nitrogen availability, with the latter having strongest direct effects. Main Conclusions The distributions of forest biodiversity and carbon storage can be modulated by distinct mycorrhizal fungi and trees. Moreover, future global changes (e.g. climate warming, intensifying nitrogen deposition) could alter the mycorrhizal‐mediated BEF relationships in mountain forests.

Appropriate oxygen vacancies and Mo-N bond synergistically modulate charge transfer dynamics of MoO3−x/S-CN for superior photocatalytic disinfection: Unveiling synergistic effects and disinfection mechanism - Ya-Ya Yang; Cheng-Gang Niu; Da-Wei Huang; Hai Guo; Hao-Peng Feng; Lu Li; Hui-Yun Liu; Qian-Qian Fan; Meng-Zhu Qin (Journal of Hazardous Materials, 2023)

Temperature-dependent mycotoxins production investigation in Alternaria infected cherry by ultra-high performance liquid chromatography and Orbitrap high resolution mass spectrometry - Yanshen Li; Ying Shao; Ya'ning Zhu; Anqi Chen; Jingyao Qu; Yonglin Gao; Sunan Lu; Pengjie Luo; Xin Mao (International Journal of Food Microbiology, 2023)

The protective role of vitamin C on intestinal damage induced by high-dose glycinin in juvenile Rhynchocypris lagowskii Dybowski - Rui Zhu; Zongyu Liu; Minghui Lu; Xueqin Wu; Xueyuan Zhao; Hong-He Wang; Ya-Nan Quan; Li-Fang Wu (Fish & Shellfish Immunology, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Hydraulic determinants of drought-induced tree mortality and changes in tree abundance between two tropical forests with different water availability - Yong-Qiang Wang; Hui-Qing Song; Ya-Jun Chen; Pei-Li Fu; Jiao-Lin Zhang; Kun-Fang Cao; Shi-Dan Zhu (Agricultural and Forest Meteorology, 2023)

Research progress of l-aspartate-α-decarboxylase and its isoenzyme in the β-alanine synthesis - Zhong-Ce Hu; Yu-Hang Tian; Jia-Li Yang; Ya-Nan Zhu; Hai-Yan Zhou; Yu-Guo Zheng; Zhi-Qiang Liu (World Journal of Microbiology and Biotechnology, 2023)

Effects of bepridil on early cardiac development of zebrafish - Ya-Lan Wei; Yu-Qing Lei; Zhou-Jie Ye; Xu-Dong Zhuang; Li-Ping Zhu; Xin-Rui Wang; Hua Cao (Cell and Tissue Research, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Stilbenes with potent cytotoxicity from the seedcases of Paeonia suffruticosa Andrews - Meng-Yue Yang; Zhao-Xiang Shao; Yue-Tong Wang; Yong-Lian Hou; Ding-Kang Zhu; Sha Chen; Ya-Hui Zhang; Fei Cao; Yong-Kui Jing; Bin Lin; Zhan-Lin Li; Da-Hong Li; et al. (Phytochemistry, 2023)

Cationic molecular probes based on aggregation-induced emission for fluorescent sensing and super-resolution imaging of insulin fibrosis - Li-Jun Mei; Cheng Fan; Chu-Ran Xu; Qi Yu; Chong Li; Ya-Long Wang; Ming-Qiang Zhu (Chemical Engineering Journal, 2023)

Heteroaggregation effects on Pickering stabilization using oppositely charged cellulose nanocrystal and nanochitin - Shasha Guo; Ya Zhu; Wenyang Xu; Siqi Huan; Jun Li; Tao Song; Long Bai; Orlando J. Rojas (Carbohydrate Polymers, 2023)

The cAMP‐PKA signalling pathway regulates hyphal growth, conidiation, trap morphogenesis, stress tolerance, and autophagy in Arthrobotrys oligospora - Mei‐Chen Zhu; Na Zhao; Yan‐Kun Liu; Xue‐Mei Li; Zheng‐Yi Zhen; Ya‐Qing Zheng; Ke‐Qin Zhang; Jin‐Kui Yang (Environmental Microbiology, 2022)
The cyclic adenosine monophosphate‐protein kinase A (cAMP‐PKA) signalling pathway is evolutionarily conserved in eukaryotes and plays a crucial role in defending against external environmental challenges, which can modulate the cellular response to external stimuli. Arthrobotrys oligospora is a typical nematode‐trapping fungus that specializes in adhesive networks to kill nematodes. To elucidate the biological roles of the cAMP‐PKA signalling pathway, we characterized the orthologous adenylate cyclase AoAcy, a regulatory subunit (AoPkaR), and two catalytic subunits (AoPkaC1 and AoPkaC2) of PKA in A. oligospora by gene disruption, transcriptome, and metabolome analyses. Deletion of Aoacy significantly reduced the levels of cAMP and arthrobotrisins. Results revealed that Aoacy , AopkaR , and AopkaC1 were involved in hyphal growth, trap morphogenesis, sporulation, stress resistance, and autophagy. In addition, Aoacy and AopkaC1 were involved in the regulation of mitochondrial morphology, thereby affecting energy metabolism, whereas AopkaC2 affected sporulation, nuclei, and autophagy. Multi‐omics results showed that the cAMP‐PKA signalling pathway regulated multiple metabolic and cellular processes. Collectively, these data highlight the indispensable role of cAMP‐PKA signalling pathway in the growth, development, and pathogenicity of A. oligospora, and provide insights into the regulatory mechanisms of signalling pathways in sporulation, trap formation, and lifestyle transition.

The association between hearing threshold and urinary personal care and consumer product metabolites in middle-aged and elderly people from the USA - Yan-Peng Fu; Wen-Yu Chen; Li-Qing Guo; Ya-Qiong Zhu; Jia-Sheng Yuan; Yue-Hui Liu (Environmental Science and Pollution Research, 2022)

Siccirubricoccus soli sp. nov., a novel bacterial species isolated from Jiaozi Mountain soil - Guo-Xing Zhu; Ya-Jie Wu; Yan-Ru Cao; Bing-Jun Fan; Yu Jiao; Xiu-Li Hou; Zi-Chao Liu; Yue Zhang; Jiang-Bo He; Lian-Ming Liang (Antonie van Leeuwenhoek, 2022)

A Rapid Near-Infrared Fluorescent Probe for Cysteine Based on Isophorone and its Application in B16 Cell Imaging - Yan-Ya Wang; Xue-Shuang Yu; Xin-Jie Li; Hong-Bo Liu; Xi Zhu; Ya-Wen Wang; Yu Peng (Journal of Fluorescence, 2022)

Multitrophic diversity and biotic associations influence subalpine forest ecosystem multifunctionality - Ya‐Huang Luo; Marc W. Cadotte; Jie Liu; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Jia‐Yun Zou; Zhong‐Zheng Chen; Xue‐Long Jiang; Juan Li; Kun Xu; De‐Zhu Li; et al. (Ecology, 2022)
Biodiversity across multiple trophic levels is required to maintain multiple ecosystem functions. Yet it remains unclear how multitrophic diversity and species interactions regulate ecosystem multifunctionality. Here, combining data from 9 different trophic groups (including trees, shrubs, herbs, leaf mites, small mammals, bacteria, pathogenic fungi, saprophytic fungi, and symbiotic fungi) and 13 ecosystem functions related to supporting, provisioning, and regulating services, we used a multitrophic perspective to evaluate the effects of elevation, diversity, and network complexity on scale‐dependent subalpine forest multifunctionality. Our results demonstrated that elevation and soil pH significantly modified species composition and richness across multitrophic groups and influenced multiple functions simultaneously. We present evidence that species richness across multiple trophic groups had stronger effects on multifunctionality than species richness at any single trophic level. Moreover, biotic associations, indicating the complexity of trophic networks, were positively associated with multifunctionality. The relative effects of diversity on multifunctionality increased at the scale of the larger community compared to a scale accounting for neighboring interactions. Our results highlight the paramount importance of scale‐ and context‐dependent multitrophic diversity and interactions for a better understanding of mountain ecosystem multifunctionality in a changing world.

REGγ drives Lgr5+ stem cells to potentiate radiation induced intestinal regeneration - Xiangzhan Zhu; Minglei Yang; Zaijun Lin; Solomon Kibreab Mael; Ya Li; Lili Zhang; Yaqi Kong; Yaodong Zhang; Yuping Ren; Jianhui Li; Zimeng Wang; Ying Zhang; et al. (Science China Life Sciences, 2022)

Inhibition of visfatin alleviates sepsis-induced intestinal damage by inhibiting Hippo signaling pathway - Zhong-Shen Kuang; Yu-Xin Leng; Ning Yang; Zheng-Qian Li; Ya-Nan Zong; Deng-Yang Han; Yue Li; Jin-Dan He; Xing-Ning Mi; Zhu-Kai Cong; Xi Zhu; Chang-Yi Wu; et al. (Inflammation Research, 2022)
Background The aim of this study is to investigate role of Visfatin, one of the pro-inflammatory adipokines, in sepsis-induced intestinal injury and to clarify the potential mechanism. Methods C57BL/6 mice underwent cecal ligation and puncture (CLP) surgery to establish sepsis model in vivo. Intestinal epithelial cells were stimulated with LPS to mimic sepsis-induced intestinal injury in vitro. FK866 (the inhibitor of Visfatin) with or without XMU-MP-1 (the inhibitor of Hippo signaling) was applied for treatment. The expression levels of Visfatin, NF-κB and Hippo signaling pathways-related proteins were detected by western blot or immunohistochemistry. The intestinal cell apoptosis and intestinal injury were investigated by TUNEL staining and H&E staining, respectively. ELISA was used to determine the production of inflammatory cytokines. Results The expression of Visfatin increased in CLP mice. FK866 reduced intestinal pathological injury, inflammatory cytokines production, and intestinal cell apoptosis in sepsis mice. Meanwhile, FK866 affected NF-κB and Hippo signaling pathways. Additionally, the effects of FK866 on inflammatory response, apoptosis, Hippo signaling and NF-κB signaling were partly abolished by XMU-MP-1, the inhibitor of Hippo signaling. In vitro experiments also revealed that FK866 exhibited a protective role against LPS-induced inflammatory response and apoptosis in intestinal cells, as well as regulating NF-κB and Hippo signaling, whereas addition of XMU-MP-1 weakened the protective effects of FK866. Conclusion In short, this study demonstrated that inhibition of Visfatin might alleviate sepsis-induced intestinal injury through Hippo signaling pathway, supporting a further research on Visfatin as a therapeutic target.

The study of schizogenous formation of secretory ducts in Ferula ferulaeoides (Steud.) Korov. - Meng-meng Liu; Yuan-yuan Zhao; Ying Ma; Shuang-shuang Liu; Jia-qi Yao; Ya-ping Chi; Hui-fang Li; Kai Liao; Yun Zhu (Protoplasma, 2022)

Isolation and characterization of 112 SNP markers in Yellowfin seabream (Acanthopagrus latus) using RAD sequencing - Ke-Cheng Zhu; Ya-Ling Li; Wei-Bin Wu; Bao-Suo Liu; Hua-Yang Guo; Nan Zhang; Liang Guo; Dian-Chang Zhang (Conservation Genetics Resources, 2022)

Similarity and Dissimilarity Regularized Nonnegative Matrix Factorization for Single-Cell RNA-seq Analysis - Ya-Li Zhu; Sha-Sha Yuan; Jin-Xing Liu (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Using data-limited approaches to assess data-rich Indian Ocean bigeye tuna: Data quantity evaluation and critical information for management implications - Ya’nan Li; Jiangfeng Zhu; Xiaojie Dai; Dan Fu; Yong Chen (Acta Oceanologica Sinica, 2022)

Chemical composition and anti-hepatoma effect of Annona squamosa L. pericarp oil - Ya-Yun Chen; Fu-Qiang Li; Xiao-Li Zhu; Jian-Wei Chen; Xiang Li (Natural Product Research, 2022)

Enhanced photosynthetic nitrogen use efficiency and increased nitrogen allocation to photosynthetic machinery under cotton domestication - Zhang-Ying Lei; Heng Wang; Ian J. Wright; Xin-Guang Zhu; Ülo Niinemets; Zi-Liang Li; Dong-Sheng Sun; Ning Dong; Wang-Feng Zhang; Zhong-Li Zhou; Fang Liu; Ya-Li Zhang (Photosynthesis Research, 2021)

Antimicrobial Natural Products Produced by Soil-Derived Fungus Penicillium cremeogriseum W1-1 - Xu-Yan Sang; Zhao-Jie Wang; Ya-Bin Yang; Yong-Liang Wang; Mei-Ling Xiang; Dou-Ying Zhu; Ying Zhou; Xiao-Dong Luo; Li-Xing Zhao (Indian Journal of Microbiology, 2021)

Research on support method in soft rock tunnel considering the rheological characteristics of rock - Xiao-long Guo; Yong-quan Zhu; Zhong-sheng Tan; Lei Li; Ang Li; Ya-tao Yan (Arabian Journal of Geosciences, 2021)

Novel Alcaligenes ammonioxydans sp. nov. from wastewater treatment sludge oxidizes ammonia to N 2 with a previously unknown pathway - Meng‐Ru Wu; Ting‐Ting Hou; Ying Liu; Li‐Li Miao; Guo‐Min Ai; Lan Ma; Hai‐Zhen Zhu; Ya‐Xin Zhu; Xi‐Yan Gao; Craig W. Herbold; Michael Wagner; De‐Feng Li; et al. (Environmental Microbiology, 2021)
Summary Heterotrophic nitrifiers are able to oxidize and remove ammonia from nitrogen‐rich wastewaters but the genetic elements of heterotrophic ammonia oxidation are poorly understood. Here, we isolated and identified a novel heterotrophic nitrifier, Alcaligenes ammonioxydans sp. nov. strain HO‐1, oxidizing ammonia to hydroxylamine and ending in the production of N 2 gas. Genome analysis revealed that strain HO‐1 encoded a complete denitrification pathway but lacks any genes coding for homologous to known ammonia monooxygenases or hydroxylamine oxidoreductases. Our results demonstrated strain HO‐1 denitrified nitrite (not nitrate) to N 2 and N 2 O at anaerobic and aerobic conditions respectively. Further experiments demonstrated that inhibition of aerobic denitrification did not stop ammonia oxidation and N 2 production. A gene cluster ( dnfT1RT2ABCD ) was cloned from strain HO‐1 and enabled E . coli accumulated hydroxylamine. Sub‐cloning showed that genetic cluster dnfAB or dnfABC already enabled E . coli cells to produce hydroxylamine and further to 15 N 2 from ( 15 NH 4 ) 2 SO 4 . Transcriptome analysis revealed these three genes dnfA , dnfB and dnfC were significantly upregulated in response to ammonia stimulation. Taken together, we concluded that strain HO‐1 has a novel dnf genetic cluster for ammonia oxidation and this dnf genetic cluster encoded a previously unknown pathway of di rect amm onia ox idation (Dirammox) to N 2 .

Combined use of high-resolution dialysis, diffusive gradient in thin films (DGT) technique, and conventional methods to assess trace metals in reservoir sediments - Eyram Norgbey; Yiping Li; Ya Zhu; Amechi S. Nwankwegu; Robert Bofah-Buah; Linda Nuamah; Yashuai Pu (Environmental Monitoring and Assessment, 2021)

Oceanobacillus salinisoli sp. nov., a bacterium isolated from saline soil of Turpan city in Xinjiang province, north–west China - Wen-Yong Zhu; Li Yang; Zhou-Tian-Le Zhang; Chang-Gai Mu; Yun Wang; Ya-Rong Kou; Gang-Qiang Jiang; Min Yin; Shu-Kun Tang (Archives of Microbiology, 2021)

A new epimer of azaphilone derivative pinophilin B from the gorgonian-derived fungus Aspergillus fumigatus 14–27 - Ya-Hui Zhang; Xiao-Yue Peng; Li-Xi Feng; Hua-Jie Zhu; Fei Cao; Chang-Yun Wang (Natural Product Research, 2021)

Estimation of mountain block recharge on the northern Tianshan Mountains using numerical modeling - Jian-hua Ping; Ya-qiang Zhu; Xue-mei Mei; Wei Leng; Sheng Li; Ji-chang Zhao (Journal of Mountain Science, 2021)

Iron, thermal stratification, Eucalyptus sp., and hypoxia: drivers to water blackening in southern China reservoirs - Yiping Li; Eyram Norgbey; Ya Zhu; Amechi S. Nwankwegu; Robert Bofah-Buoh; Desmond Anim; Georgina Esi Takyi- Annan; Linda Nuamah; Patrick Banahene; Yashui Pu; Yanan Huang (Environmental Science and Pollution Research, 2021)

Haloechinothrix aidingensis sp. nov., an actinomycete isolated from salt lake in Xinjiang province, north-west China - Li Yang; Ya-Rong Kou; Tong-Wei Guan; Min Yin; Bing-Bing Liu; Yong-Jiang Shi; Wen-Yong Zhu; Shu-Kun Tang (Archives of Microbiology, 2021)

The circular RNA circSlc7a11 promotes bone cancer pain pathogenesis in rats by modulating LLC-WRC 256 cell proliferation and apoptosis - Han-Wen Chen; Xiao-Xia Zhang; Zhu-Ding Peng; Zu-Min Xing; Yi-Wen Zhang; Ya-Lan Li (Molecular and Cellular Biochemistry, 2021)
Treatment of bone cancer pain (BCP) caused by bone metastasis in advanced cancers remains a challenge in clinical oncology, and the underlying mechanisms of BCP are poorly understood. This study aimed to investigate the pathogenic roles of circular RNAs (circRNAs) in regulating cancer cell proliferation and BCP development. Eight differentially expressed circRNAs in the rat spinal cord were validated by agarose gel electrophoresis and Sanger sequencing. Expression of circRNAs and mRNAs was detected by quantitative RT-PCR. MTS assay and flow cytometry were performed to analyze cell proliferation and apoptosis, respectively. Differentially expressed mRNA profiles were characterized by deep RNA sequencing, hierarchical clustering, and functional categorization. The interactions among circRNAs, microRNAs (miRNAs), and mRNAs were predicted using TargetScan. Additionally, western blot was performed to determine the protein levels of Pax8, Isg15, and Cxcl10. Multiple circRNAs were differentially expressed in the spinal cords of BCP model rats; of these, circSlc7a11 showed the greatest increase in expression. The overexpression of circSlc7a11 significantly promoted cell proliferation and repressed apoptosis of LLC-WRC 256 and UMR-106 cells, whereas circSlc7a11 silencing produced the opposite effects. Altered expression of circSlc7a11 also induced substantial changes in the mRNA expression profiles of LLC-WRC 256 cells; these changes were linked to multiple apoptotic processes and signaling pathways, such as the chemokine signaling pathway, and formed a complex circRNA/miRNA/mRNA network. Additionally, Pax8, Isg15, and Cxc110 protein level in LLC-WRC 256 cells was consistent with the mRNA results. The circRNA circSlc7a11 regulates rat BCP development by modulating LLC-WRC 256 cell proliferation and apoptosis through multiple-signaling mechanisms.

Influence of the roots of mixed-planting species on the shear strength of saline loess soil - Ya-bin Liu; Xia-song Hu; Dong-mei Yu; Hai-li Zhu; Guo-rong Li (Journal of Mountain Science, 2021)

The disruption of the MAPKK gene triggering the synthesis of flavonoids in endophytic fungus Phomopsis liquidambaris - Qian Yang; Mei Wu; Ya-Li Zhu; Ya-Qiong Yang; Yan-Zhen Mei; Chuan-Chao Dai (Biotechnology Letters, 2021)

Paenibacillus turpanensis sp. nov., isolated from a salt lake of Turpan city in Xinjiang province, north-west China - Li Yang; Hua-Wei Huang; Yun Wang; Ya-Rong Kou; Min Yin; Yu Li; Xue-Qian Wang; Gui-Fang Zhao; Wen-Yong Zhu; Shu-Kun Tang (Archives of Microbiology, 2021)

Toxicity Changes of Heavily Polluted River Sediments on Daphnia magna Before and After Dredging - Li-Ling Zhang; Zhou-Tao Pei; Ya-Ni Zhao; Jing Zhang; Rou-Rou Xu; Meng Zhang; Wen-Qiang Wang; Li-Wei Sun; Guang-Can Zhu (Bulletin of Environmental Contamination and Toxicology, 2020)

Abnormal synchronization of functional and structural networks in schizophrenia - Jiajia Zhu; Yinfeng Qian; Biao Zhang; Xiaohu Li; Ya Bai; Xiaoshu Li; Yongqiang Yu (Brain Imaging and Behavior, 2020)

Aluminum and magnesium status during pregnancy and placenta oxidative stress and inflammatory mRNA expression: China Ma’anshan birth cohort study - Jian-Qing Wang; Ya-Bin Hu; Chun-Mei Liang; Xun Xia; Zhi-Juan Li; Hui Gao; Jie Sheng; Kun Huang; Su-Fang Wang; Yan Li; Peng Zhu; Jia-Hu Hao; et al. (Environmental Geochemistry and Health, 2020)

Anxiolytic Effect of Increased NREM Sleep after Acute Social Defeat Stress in Mice - Xiang Feng; Hui-Ying Zhao; Yu-Jin Shao; Hui-Fang Lou; Li-Ya Zhu; Shumin Duan; Yan-Qin Yu (Neuroscience Bulletin, 2020)
Social defeat stress (SDS) plays a major role in the pathogenesis of psychiatric disorders like anxiety and depression. Sleep is generally considered to involve recovery of the brain from prior experience during wakefulness and is altered after acute SDS. However, the effect of acute SDS on sleep/wake behavior in mice varies between studies. In addition, whether sleep changes in response to stress contribute to anxiety is not well established. Here, we first investigated the effects of acute SDS on sleep/wake states in the active period in mice. Our results showed that total sleep time (time in rapid eye-movement [REM] and non-REM [NREM] sleep) increased in the active period after acute SDS. NREM sleep increased mainly during the first 3 h after SDS, while REM sleep increased at a later time. Then, we demonstrated that the increased NREM sleep had an anxiolytic benefit in acute SDS. Mice deprived of sleep for 1 h or 3 h after acute SDS remained in a highly anxious state, while in mice with ad libitum sleep the anxiety rapidly faded away. Altogether, our findings suggest an anxiolytic effect of NREM sleep, and indicate a potential therapeutic strategy for anxiety.

A study on the occurrence of black water in reservoirs in Eucalyptus Plantation region - Fan Luo; Yiping Li; Eyram Norgbey; Ronghui Li; Zhu Ya; Amechi S. Nwankwegu; Huang Lie; Linda Sarpong (Environmental Science and Pollution Research, 2020)

Tyrosine Hydroxylase Gene Polymorphisms Contribute to Opioid Dependence and Addiction by Affecting Promoter Region Function - Jun-lin Liu; Shao-qing Li; Feng Zhu; Yu-xiang Zhang; Ya-nan Wu; Jing-si Yang; Bao Zhang; Chun-xia Yan (NeuroMolecular Medicine, 2020)

Initial chest CT findings in COVID-19: correlation with clinical features - Zhu-jing Shen; Nan Lu; Lu-lu Gao; Jian Lv; Hua-fu Luo; Ji-feng Jiang; Chao Xu; Shi-ya Li; Ju-jiang Mao; Kai Li; Xiao-pei Xu; Bin Lin (Journal of Zhejiang University-SCIENCE B, 2020)

Oceanobacillus halotolerans sp. nov., a bacterium isolated from salt lake in Xinjiang province, north-west China - Wen-Yong Zhu; Li Yang; Yong-Jiang Shi; Chang-Gai Mu; Yun Wang; Ya-Rong Kou; Min Yin; Shu-Kun Tang (Archives of Microbiology, 2020)

Nitric Oxide Negatively Regulates Larval Metamorphosis in Hard-Shelled Mussel (Mytilus coruscus) - You-Ting Zhu; Ya Zhang; Yu-Zhu Liu; Yi-Feng Li; Asami Yoshida; Kiyoshi Osatomi; Jin-Long Yang; Xiao Liang (Frontiers in Marine Science, 2020)

Leukocyte immunoglobulin-like receptor B4 protects against cardiac hypertrophy via SHP-2-dependent inhibition of the NF-κB pathway - Heng Zhou; Ning Li; Yuan Yuan; Ya-Ge Jin; Qingqing Wu; Ling Yan; Zhou-Yan Bian; Wei Deng; Di-Fei Shen; Hongliang Li; Qi-Zhu Tang (Journal of Molecular Medicine, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Serum Uric Acid Levels and Risk of Intracranial Atherosclerotic Stenosis: A Cross-Sectional Study - Lin Li; Jun-Xia Zhu; Xiao-He Hou; Ya-Hui Ma; Wei Xu; Chen-Chen Tan; Fu-Rong Sun; Hong-Qi Li; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Thioredoxin-Interacting Protein (TXNIP) Regulates Parkin/PINK1-mediated Mitophagy in Dopaminergic Neurons Under High-glucose Conditions: Implications for Molecular Links Between Parkinson’s Disease and Diabetes - Cun-Jin Su; Zhu Shen; Ru-Xiao Cui; Ya Huang; De-Lai Xu; Feng-Lun Zhao; Jie Pan; Ai-Ming Shi; Tong Liu; Yun-Li Yu (Neuroscience Bulletin, 2020)

An on-demand construction method of disaster scenes for multilevel users - Weilian Li; Jun Zhu; Yunhao Zhang; Lin Fu; Yuhang Gong; Ya Hu; Yungang Cao (Natural Hazards, 2020)

Applying multivariate statistics for identification of groundwater chemistry and qualities in the Sugan Lake Basin, Northern Qinghai-Tibet Plateau, China - Juan Xiang; Jun-ju Zhou; Jun-cang Yang; Mei-hua Huang; Wei Feng; Qiao-qiao Li; Dong-xiang Xue; Ya-ru Zhao; Guo-feng Zhu (Journal of Mountain Science, 2020)

The efflux pump inhibitor tetrandrine exhibits synergism with fluconazole or voriconazole against Candida parapsilosis - Ya-Jing Zhao; Wei-Da Liu; Yong-Nian Shen; Dong-Mei Li; Kun-Ju Zhu; Hong Zhang (Molecular Biology Reports, 2019)

Rapid adaptation of Brachionus angularis (Rotifera) to invasion by Brachionus calyciflorus - Yi-Long Xi; Ke-Qiang Huang; Ling Pan; Han Zhu; Ya-Li Ge; Xin-Li Wen; Xian-Ling Xiang (Hydrobiologia, 2019)

Carbon-based magnetic nanocomposite as catalyst for persulfate activation: a critical review - Ya Pang; Kun Luo; Lin Tang; Xue Li; Jiangfang Yu; Junyuan Guo; Yuanyuan Liu; Zhu Zhang; Ran Yue; Ling Li (Environmental Science and Pollution Research, 2019)

Performance and Spatial Distribution of Functional Bacteria under Low-Temperature Stress in Biofilm Systems for Polluted Source Water Pretreatment - Guang-feng Yang; Li-juan Feng; Jun Mu; Jing-ya Sun; Liang Zhu; Xiang-yang Xu (International Journal of Environmental Research, 2019)

Influence of Different Propulsion Speeds on the Characteristics of Mine Pressure in the Fully Mechanized Caving Face During Rotary Stage - Liang Li; Xue He; Yong-qiang Chen; Ya-chun Li; Chen-hao Shi; Yu-ping Zhu (Geotechnical and Geological Engineering, 2019)

Forest community assembly is driven by different strata‐dependent mechanisms along an elevational gradient - Ya‐Huang Luo; Marc W. Cadotte; Kevin S. Burgess; Jie Liu; Shao‐Lin Tan; Kun Xu; De‐Zhu Li; Lian‐Ming Gao (Journal of Biogeography, 2019)
Aim The mechanisms driving forest community assembly along elevational gradients remain elusive. The distinct strata in heterogeneous forest are subject to differing assembly mechanisms. This study aims to evaluate how different ecological mechanisms driving forest community assembly across strata and spatial scales, and to identify how these assemblages respond to different abiotic or biotic variables along an elevational gradient. Location Yulong Mountain within Hengduan Mountains, Southwest China. Taxon Seed plants. Methods We sampled plant species along a 1,200 m elevational gradient across forest strata (trees, shrubs and herbs) at different spatial scales (neighbourhood and community). We integrated phylogenetic and functional diversity to disentangle the roles of ecological mechanisms in structuring community assembly. We also determined the relative effects of climatic, soil and biotic variables and their interactions on these community assemblages. Results The phylogenetic and functional diversity of trees were lower at the extremes of the elevational gradient, where they were constrained by water availability or temperature. While communities with higher species diversity exhibited an overdispersed structure at mid‐elevations. For shrubs, overdispersion was exhibited at high elevations despite low species richness, which could be consistent with facilitative interactions or competition exclusion. However, most communities of herbs appear to have a markedly random structure, despite some incongruence between phylogenetic divergence and functional convergence, as well as influences from overstorey trees and local light conditions. The relative effects of abiotic variables on community structure were larger at the community scale than at the neighbourhood scale. Main conclusions Our study emphasises the importance of considering phylogenies and traits in understanding the strata‐ and scale‐dependent mechanisms of forest community assembly. Collectively, results indicate that contrasting assembly mechanisms interact across different strata along elevational gradients to shape diverse forest communities.

Greater than the sum of the parts: how the species composition in different forest strata influence ecosystem function - Ya‐Huang Luo; Marc W. Cadotte; Kevin S. Burgess; Jie Liu; Shao‐Lin Tan; Jia‐Yun Zou; Kun Xu; De‐Zhu Li; Lian‐Ming Gao (Ecology Letters, 2019)
The mechanisms underpinning forest biodiversity‐ecosystem function relationships remain unresolved. Yet, in heterogeneous forests, ecosystem function of different strata could be associated with traits or evolutionary relationships differently. Here, we integrate phylogenies and traits to evaluate the effects of elevational diversity on above‐ground biomass across forest strata and spatial scales. Community‐weighted means of height and leaf phosphorous concentration and functional diversity in specific leaf area exhibited positive correlations with tree biomass, suggesting that both positive selection effects and complementarity occur. However, high shrub biomass is associated with greater dissimilarity in seed mass and multidimensional trait space, while species richness or phylogenetic diversity is the most important predictor for herbaceous biomass, indicating that species complementarity is especially important for understory function. The strength of diversity‐biomass relationships increases at larger spatial scales. We conclude that strata‐ and scale‐ dependent assessments of community structure and function are needed to fully understand how biodiversity influences ecosystem function.

Tolerance of two apple rootstocks to short-term salt stress: focus on chlorophyll degradation, photosynthesis, hormone and leaf ultrastructures - Yan-fang Zhu; Yu-xia Wu; Ya Hu; Xu-mei Jia; Tong Zhao; Li Cheng; Yan-xiu Wang (Acta Physiologiae Plantarum, 2019)

Polymorphism analyses of 19 STRs in Labrador Retriever population from China and its heterozygosity comparisons with other retriever breeds - Meng-Lei Wang; Xiao-Ye Jin; Xin Xiong; Jin-Long Yang; Jian-Ping Li; Qi Wang; Bo-Feng Zhu; Ya-Jun Deng (Molecular Biology Reports, 2019)

Long noncoding RNA UCA1 promotes the proliferation of hypoxic human pulmonary artery smooth muscle cells - Tian-Tian Zhu; Rui-Li Sun; Ya-Ling Yin; Jin-Ping Quan; Ping Song; Jian Xu; Ming-Xiang Zhang; Peng Li (Pflügers Archiv - European Journal of Physiology, 2019)

Chronic Intracerebroventricular Infusion of Metformin Inhibits Salt-Sensitive Hypertension via Attenuation of Oxidative Stress and Neurohormonal Excitation in Rat Paraventricular Nucleus - Xiao-Jing Yu; Ya-Nan Zhao; Yi-Kang Hou; Hong-Bao Li; Wen-Jie Xia; Hong-Li Gao; Kai-Li Liu; Qing Su; Hui-Yu Yang; Bin Liang; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Sesquiterpenes and lignans from the flower buds of Daphne genkwa and their nitric oxide inhibitory activities - Chun-Yang Zhang; Lan Luo; Jing Xia; Ya-Nan Song; Li-Jun Zhang; Miao Zhang; Khalid Rahman; Yin Ye; Hong Zhang; Jian-Yong Zhu (Natural Product Research, 2018)

Transcriptome analysis in Malus halliana roots in response to iron deficiency reveals insight into sugar regulation - Ya Hu; Yan-fang Zhu; Ai-xia Guo; Xu-mei Jia; Li Cheng; Tong Zhao; Yan-xiu Wang (Molecular Genetics and Genomics, 2018)

Development and characterization of 27 SNP markers in the Mauremys mutica transcriptome - Zhang Xin-Cheng; Zhao Jian; Li Wei; Liu Yi-Hui; Wei Cheng-Qing; Wang Ya-Kun; Ye Zhao-Yang; Zhu Xin-Ping (Conservation Genetics Resources, 2018)

Cryo-EM structure reveals cylindrical nucleocapsids from two polydnaviruses - Ji-Hui Cui; Ya-Bin Chen; Ming Li; Qiu-Chen Cai; Li-Dan Zhang; Zi-Yun Lu; Jian-Cheng Li; Qi-Shun Zhu; Gang Ji; Kai-Jun Luo (Archives of Virology, 2018)

Preference and performance of the two-spotted spider mite Tetranychus urticae (Acari: Tetranychidae) on strawberry cultivars - Ya-Jun Gong; Jin-Cui Chen; Liang Zhu; Li-Jun Cao; Gui-Hua Jin; Ary A. Hoffmann; Chuan-Fei Zhong; Peng Wang; George Lin; Shu-Jun Wei (Experimental and Applied Acarology, 2018)

Molecular insights into brown rust resistance and potential epidemic based on the Bru1 gene in sugarcane varieties and new elite clones - Zhu Li; Ya-Chun Su; Qing Yu; Yun Chen; Shi-Wu Gao; Yong-Gang Zhang; You-Xiong Que; Li-Ping Xu (Euphytica, 2018)

Testing Darwin's transoceanic dispersal hypothesis for the inland nettle family (Urticaceae) - Zeng‐Yuan Wu; Jie Liu; Jim Provan; Hong Wang; Chia‐Jui Chen; Marc W. Cadotte; Ya‐Huang Luo; Bruno S. Amorim; De‐Zhu Li; Richard I. Milne (Ecology Letters, 2018)
Dispersal is a fundamental ecological process, yet demonstrating the occurrence and importance of long‐distance dispersal ( LDD ) remains difficult, having rarely been examined for widespread, non‐coastal plants. To address this issue, we integrated phylogenetic, molecular dating, biogeographical, ecological, seed biology and oceanographic data for the inland Urticaceae. We found that Urticaceae originated in Eurasia c . 69 Ma, followed by ≥ 92 LDD events between landmasses. Under experimental conditions, seeds of many Urticaceae floated for > 220 days, and remained viable after 10 months in seawater, long enough for most detected LDD events, according to oceanographic current modelling. Ecological traits analyses indicated that preferences for disturbed habitats might facilitate LDD . Nearly half of all LDD events involved dioecious taxa, so population establishment in dioecious Urticaceae requires multiple seeds, or occasional selfing. Our work shows that seawater LDD played an important role in shaping the geographical distributions of Urticaceae, providing empirical evidence for Darwin's transoceanic dispersal hypothesis.

CFTR prevents neuronal apoptosis following cerebral ischemia reperfusion via regulating mitochondrial oxidative stress - Ya-Ping Zhang; Yong Zhang; Zhi-Bin Xiao; Yan-Bo Zhang; Jing Zhang; Zhi-Qiang Li; Yao-Bin Zhu (Journal of Molecular Medicine, 2018)

The complete mitochondrial genome of Kele pig (Sus scrofa) using next-generation deep sequencing - Ya Tan; Kai-zhi Shi; Jing Wang; Chun-lin Du; Chun-ping Zhao; Xiong Zhang; Li Zhu; Yi-shun Shang (Conservation Genetics Resources, 2018)

MiR-181b Antagonizes Atherosclerotic Plaque Vulnerability Through Modulating Macrophage Polarization by Directly Targeting Notch1 - Tian-Hui An; Quan-Wei He; Yuan-Peng Xia; Sheng-Cai Chen; Suraj Baral; Ling Mao; Hui-Juan Jin; Ya-Nan Li; Meng-Die Wang; Jian-Guo Chen; Ling-Qiang Zhu; Bo Hu (Molecular Neurobiology, 2017)

RETRACTED ARTICLE: Autophagy regulated by lncRNA HOTAIR contributes to the cisplatin-induced resistance in endometrial cancer cells - Meng-Yao Sun; Jian-Yong Zhu; Chun-Yan Zhang; Miao Zhang; Ya-Nan Song; Khalid Rahman; Li-Jun Zhang; Hong Zhang (Biotechnology Letters, 2017)

Toxicity comparison of different active fractions extracted from radix Sophorae tonkinensis in zebrafish - Hong-cui Liu; Xiao-yu Zhu; Jiang-hua Chen; Sheng-ya Guo; Chun-qi Li; Zhong-ping Deng (Journal of Zhejiang University-SCIENCE B, 2017)

Mangiferin Upregulates Glyoxalase 1 Through Activation of Nrf2/ARE Signaling in Central Neurons Cultured with High Glucose - Yao-Wu Liu; Ya-Qin Cheng; Xiao-Li Liu; Yun-Chao Hao; Yu Li; Xia Zhu; Fan Zhang; Xiao-Xing Yin (Molecular Neurobiology, 2017)

Molecular identification of differential expression genes associated with sex pheromone biosynthesis in Spodoptera exigua - Ya-Nan Zhang; Long-Wa Zhang; Da-Song Chen; Liang Sun; Zhao-Qun Li; Zhan-Feng Ye; Mei-Yan Zheng; Jin-Bu Li; Xiu-Yun Zhu (Molecular Genetics and Genomics, 2017)

Environmental change and raw material selection strategies at Taoshan: a terminal Late Pleistocene to Holocene site in north‐eastern China - Shi‐Xia Yang; Yu‐Xiu Zhang; You‐Qian Li; Chao Zhao; Xiao‐Qiang Li; Jian‐Ping Yue; Ya‐Mei Hou; Cheng‐Long Deng; Ri‐Xiang Zhu; Michael D. Petraglia (Journal of Quaternary Science, 2017)
The Lesser Khingan Mountains of north‐eastern China are heavily forested, making archaeological site identification difficult owing to poor ground surface visibility. Nevertheless, several prehistoric archaeological site discoveries have been made in recent years and a limited number of excavations have been initiated. One of the most important sites to emerge is Taoshan, which has yielded stratified stone tool assemblages dating from the Last Glacial Maximum (LGM) to the mid‐Holocene. Pollen profiles indicate significant changes in vegetation, fluctuating from steppe conditions during the LGM to forested conditions in the Bølling–Allerød interstadial (B–A) and the mid‐Holocene. The stone tool assemblages from Taoshan were primarily produced from varieties of volcanic tuff, rhyolite, hornfels and agate. Geological prospecting and petrological analyses were performed to document procurement sources and changes in raw material exploitation strategies. During the LGM, the predominant raw material was vitric tuff, available from a source ca. 5–10 km from Taoshan. In the B–A and mid‐Holocene layers, emphasis was on the exploitation of raw materials in gravel bars, although stone tool reduction techniques and raw material preferences changed considerably during this time interval. Diachronic changes in raw materials and exploitation strategies correspond to changes in vegetation and human adaptations.

The Research on the Relationship of RAGE, LRP-1, and Aβ Accumulation in the Hippocampus, Prefrontal Lobe, and Amygdala of STZ-Induced Diabetic Rats - Lou-Yan Ma; Yu-Lang Fei; Xiao-Ye Wang; Song-Di Wu; Jun-Hui Du; Mei Zhu; Long Jin; Ming Li; Hai-Long Li; Jia-Jia Zhai; Lu-Peng Ji; Ran-Ran Ma; et al. (Journal of Molecular Neuroscience, 2017)

Effects of melanocortin-4 receptor agonists and antagonists on expression of genes related to reproduction in spotted scat, Scatophagus argus - Dong-Neng Jiang; Jian-Tao Li; Ya-Xiong Tao; Hua-Pu Chen; Si-Ping Deng; Chun-Hua Zhu; Guang-Li Li (Journal of Comparative Physiology B, 2017)

Monazite RW-1: a homogenous natural reference material for SIMS U–Pb and Th–Pb isotopic analysis - Xiao-Xiao Ling; Magdalena H. Huyskens; Qiu-Li Li; Qin-Zhu Yin; Ronald Werner; Yu Liu; Guo-Qiang Tang; Ya-Nan Yang; Xian-Hua Li (Mineralogy and Petrology, 2017)

Glucocorticoids Prevent Enterovirus 71 Capsid Protein VP1 Induced Calreticulin Surface Exposure by Alleviating Neuronal ER Stress - Dan-Dan Hu; Jian-Ning Mai; Li-Ya He; Pei-Qing Li; Wen-Xiong Chen; Jian-Jiang Yan; Wei-Dong Zhu; Li Deng; Dan Wei; Di-Hui Liu; Si-Da Yang; Zhi-Bin Yao (Neurotoxicity Research, 2017)

GPR30 Activation Contributes to the Puerarin-Mediated Neuroprotection in MPP+-Induced SH-SY5Y Cell Death - Yue-Fa Cheng; Guoqi Zhu; Qing-Wen Wu; Yue-Sheng Xie; Yan Jiang; Lan Guo; Ya-Li Guan; Ying-Shuo Liu; Jun Zhang (Journal of Molecular Neuroscience, 2017)

Microsatellite records for volume 8, issue 4 - Alejandra Paola Ojeda; Alexandre Wagner Silva Hilsdorf; Ana Caroline Leite; Ao-ao Yang; Ayako Izuno; Chongbo He; Chun-ya Zhou; Daisuke Kyogoku; Danilo Caneppele; Dongmei Zhu; Fernando Stopato da Fonseca; Hao Yin; et al. (Conservation Genetics Resources, 2016)

Earth Fissures in Su–Xi–Chang Region, Jiangsu, China - Guang-ya Wang; Greg You; Jin-qi Zhu; Jun Yu; Wei Li (Surveys in Geophysics, 2016)

Combined effects of age and polymorphisms in Notch3 in the pathogenesis of cerebral infarction disease - Chun-Yu Zhu; Yue Wang; Qing-Xuan Zeng; Yu Qian; Huan Li; Zi-Xia Yang; Ya-Mei Yang; Qiong Zhang; Fei-Feng Li; Shu-Lin Liu (Metabolic Brain Disease, 2016)

Activation of mTOR signaling mediates the increased expression of AChE in high glucose condition: in vitro and in vivo evidences - Yao-Wu Liu; Liang Zhang; Yu Li; Ya-Qin Cheng; Xia Zhu; Fan Zhang; Xiao-Xing Yin (Molecular Neurobiology, 2016)

Isolation, diversity and acetylcholinesterase inhibitory activity of the culturable endophytic fungi harboured in Huperzia serrata from Jinggang Mountain, China - Ya Wang; Zheng Lai; Xi-Xi Li; Ri-Ming Yan; Zhi-Bin Zhang; Hui-Lin Yang; Du Zhu (World Journal of Microbiology and Biotechnology, 2016)

Identification of insecticidal constituents of the essential oils of Dahlia pinnata Cav. against Sitophilus zeamais and Sitophilus oryzae - Da-Cheng Wang; Da-Ren Qiu; Li-Na Shi; Hong-Yu Pan; Ya-Wei Li; Jin-Zhu Sun; Ying-Jie Xue; Dong-Sheng Wei; Xiang Li; Ya-Mei Zhang; Jian-Chun Qin (Natural Product Research, 2015)

Baseline sensitivity and control efficacy of fluazinam against Sclerotinia sclerotiorum - Hong-Jie Liang; Ya-Li Di; Jin-Li Li; Fu-Xing Zhu (European Journal of Plant Pathology, 2015)

Role of anti-inflammatory cytokines IL-4 and IL-13 in systemic sclerosis - Xiao-Lei Huang; Yu-Jie Wang; Jun-Wei Yan; Ya-Nan Wan; Bing Chen; Bao-Zhu Li; Guo-Jun Yang; Jing Wang (Inflammation Research, 2015)

Baseline sensitivity and control efficacy of DMI fungicide epoxiconazole against Sclerotinia sclerotiorum - Jin-Li Li; Xiang-Yang Liu; Ya-Li Di; Hong-Jie Liang; Fu-Xing Zhu (European Journal of Plant Pathology, 2015)

Nicotine-induced upregulation of VCAM-1, MMP-2, and MMP-9 through the α7-nAChR-JNK pathway in RAW264.7 and MOVAS cells - Zong-Zhuang Li; Zhen-Zhen Guo; Zhi Zhang; Qun-An Cao; Ya-Juan Zhu; Hua-Li Yao; Li-Li Wu; Qiu-Yan Dai (Molecular and Cellular Biochemistry, 2015)

Upregulation of HIF-1α Via Activation of ERK and PI3K Pathway Mediated Protective Response to Microwave-Induced Mitochondrial Injury in Neuron-Like Cells - Li Zhao; Yue-Feng Yang; Ya-Bing Gao; Shui-Ming Wang; Li-Feng Wang; Hong-Yan Zuo; Ji Dong; Xin-Ping Xu; Zhen-Tao Su; Hong-Mei Zhou; Ling-Ling Zhu; Rui-Yun Peng (Molecular Neurobiology, 2014)

Quantitative trait loci analysis of individual and total isoflavone contents in soybean seeds - HAI JUN ZHANG; JING WEN LI; YA JING LIU; WEN ZHU JIANG; XING LIN DU; LIN LI; XIAO WEI Li; LIAN TAI SU; QING YU WANG; YING WANG (Journal of Genetics, 2014)

Putative Pathway of Sex Pheromone Biosynthesis and Degradation by Expression Patterns of Genes Identified from Female Pheromone Gland and Adult Antenna of Sesamia inferens (Walker) - Ya-Nan Zhang; Yi-Han Xia; Jia-Yao Zhu; Sheng-Yun Li; Shuang-Lin Dong (Journal of Chemical Ecology, 2014)

Suppression of methylglyoxal hyperactivity by mangiferin can prevent diabetes-associated cognitive decline in rats - Yao-Wu Liu; Xia Zhu; Qian-Qian Yang; Qian Lu; Jian-Yun Wang; Hui-Pu Li; Ya-Qin Wei; Jia-Le Yin; Xiao-Xing Yin (Psychopharmacology, 2013)

β1-adrenoceptor gene Arg389Gly polymorphism and essential hypertension risk in general population: a meta-analysis - Hao Wang; Jielin Liu; Kuo Liu; Ya Liu; Zuoguang Wang; Yuqing Lou; Qiuli Niu; Wei Gu; Lijuan Wang; Mei Li; Xiaoling Zhu; Shaojun Wen (Molecular Biology Reports, 2013)

Persistence and intergenerational transmission of differentially expressed genes in the testes of intracytoplasmic sperm injection conceived mice - Li-ya Wang; Ning Wang; Fang Le; Lei Li; Le-jun Li; Xiao-zhen Liu; Ying-ming Zheng; Hang-ying Lou; Xiang-rong Xu; Xiao-ming Zhu; Yi-min Zhu; He-feng Huang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Paracoccus siganidrum sp. nov., isolated from fish gastrointestinal tract - Ying Liu; Qing-yi Xie; Kui Hong; Lei Li; Ya-mei Zhao; Yi-li Tang; Jun-ying An; Ping-ping Zhu; Chun-hou Xu (Antonie van Leeuwenhoek, 2013)

Cordyceps sinensis protects against renal ischemia/reperfusion injury in rats - Hua-Pin Wang; Ching-Wen Liu; Hsueh-Wen Chang; Jen-Wei Tsai; Ya-Zhu Sung; Li-Ching Chang (Molecular Biology Reports, 2013)

Preparation and evaluation of a new releasable PEGylated tumor necrosis factor-α (TNF-α) conjugate for therapeutic application - ChuanYun Dai; Ya Fu; ShaoCheng Chen; Biao Li; Bo Yao; WanHong Liu; LiQing Zhu; Nan Chen; Ji Chen; Qiang Zhang (Science China Life Sciences, 2013)

Comparative transcriptome analysis of tobacco (Nicotiana tabacum) leaves to identify aroma compound-related genes expressed in different cultivated regions - Bo Lei; Xue-Hua Zhao; Kai Zhang; Jie Zhang; Wei Ren; Zhu Ren; Yi Chen; Hui-Na Zhao; Wen-Jie Pan; Wei Chen; Hong-Xun Li; Wen-Ya Deng; et al. (Molecular Biology Reports, 2013)

An Arabidopsis mutant atcsr-2 exhibits high cadmium stress sensitivity involved in the restriction of H2S emission - Ya-wei Li; Ze-hua Gong; Yao Mu; Yi-xian Zhang; Zeng-jie Qiao; Li-ping Zhang; Zhu-ping Jin; Hua Li; Yan-xi Pei (Journal of Zhejiang University-SCIENCE B, 2012)

Development of RT-LAMP and real-time RT-PCR assays for the rapid detection of the new duck Tembusu-like BYD virus - Tao Jiang; Juan Liu; Yong-Qiang Deng; Jing-Liang Su; Li-Juan Xu; Zhi-Hui Liu; Xiao-Feng Li; Xue-Dong Yu; Shun-Ya Zhu; George Fu Gao; E-De Qin; Cheng-Feng Qin (Archives of Virology, 2012)

Quaternary palaeoenvironmental oscillations drove the evolution of the Eurasian Carassius auratus complex (Cypriniformes, Cyprinidae) - Yun Gao; Shu‐Yan Wang; Jing Luo; Robert W. Murphy; Rui Du; Shi‐Fang Wu; Chun‐Ling Zhu; Yan Li; Andrei D. Poyarkov; Sang Ngoc Nguyen; Peng‐Tao Luan; Ya‐Ping Zhang (Journal of Biogeography, 2012)
Aim We sought to reconstruct the spatio‐temporal genetic diversification in goldfish of the Carassius auratus complex, which is widely distributed in Eurasia, to test whether vicariance events or human‐mediated translocations best explained lineage divergence and genogeographical history. Location East Asia and the Oriental islands including Japan, the Ryukyus and Taiwan, and Europe, including Russia and the Czech Republic. Methods We reconstructed the matrilineal history of Eurasian goldfish using 1876 sequences from the partial mitochondrial DNA control region (426 bp) and 191 complete sequences of cytochrome b (1140 bp) from 67 localities representing most of the range of the species. Divergence times were estimated using a Bayesian Markov chain Monte Carlo approach based either on molecular clock data or on the fossil record. Genetic structure and the historical demography of populations were analysed using partial correlation tests and analyses of molecular variance. Results Three lineages had high levels of regional specificity. Lineages A and B from the main islands of Japan differed greatly from lineage C, which occurred on the mainland, Taiwan and the Ryukyus. Lineages A and B had late Pliocene origins. Six geographically constrained sublineages within lineage C had near‐simultaneous mid‐Pleistocene divergences. Main conclusions Genetic structure in the C. auratus complex appears to have been driven by palaeoenvironmental perturbations rather than human translocations. The disappearance of a land bridge in the Tsushima Strait around 3.0 Ma is responsible for the separation of Japanese and continental lineages; the estimated divergence time is 2.75–2.32 Ma. Fujian, China and Vietnam appear to have provided important refugia for the C. auratus complex during glaciation. After warm, moist summer monsoons intensified during the mid‐Pleistocene, goldfish are likely to have dispersed north‐eastwards to recolonize the Ryukyus via Taiwan and northwards to recolonize mainland China.

A new convenient technique for making cell blocks - Qing-Lian He; Ya-Zhen Zhu; Guang-Juan Zheng; Ling-Chun Shi; Shao-Wei Hu; Chu-Tian Li (Cell and Tissue Research, 2012)

Genetic and physical mapping of qHY-8, a pleiotropic QTL for heading date and yield-related traits in rice - Hai-Ya Cai; Shu Diao; Yong-Gang He; Li-Pan Zhang; Shao-Jia Liu; Ying-Guo Zhu; Zhi-Hong Zhang (Euphytica, 2012)

Molecular characterization and expression analysis on two isogenes encoding 3-deoxy-d-arabino-heptulosonate 7-phosphate synthase in grapes - Zhen-Zhen Zhang; Xiao-Xi Li; Bao-Qing Zhu; Ya-Qin Wen; Chang-Qing Duan; Qiu-Hong Pan (Molecular Biology Reports, 2011)

The role of VEGF/VEGFR2 signaling in peripheral stimulation-induced cerebral neurovascular regeneration after ischemic stroke in mice - Wen-Lei Li; Jamie L. Fraser; Shan P. Yu; Jian Zhu; Ya-Jun Jiang; Ling Wei (Experimental Brain Research, 2011)

Genetic polymorphism analysis of 15 STR loci in Chinese Hui ethnic group residing in Qinghai province of China - Ya-jun Deng; Bo-feng Zhu; Chun-mei Shen; Hong-dan Wang; Jing-feng Huang; Yuan-zhe Li; Hai-xia Qin; Hao-fang Mu; Jie Su; Jie Wu; Bo Zhang; Shuan-liang Fan (Molecular Biology Reports, 2011)

Genetic analysis of starch paste viscosity parameters in glutinous rice (Oryza sativa L.) - Chang-Jie Yan; Zhi-Xi Tian; Yu-Wei Fang; Ya-Chun Yang; Jian Li; Sheng-Yuan Zeng; Shi-Liang Gu; Chen-Wu Xu; Shu-Zhu Tang; Ming-Hong Gu (Theoretical and Applied Genetics, 2011)

Distribution and Characterization of Higher Chlorinated Benzenes in Outdoor Dust Collected from a Fast Developing City in North China - Zhong-Zhi Yang; Yong-Fang Li; Zhi-Chun Li; Yu-Mei Gu; Ya Zhu; Zhan-Jun Zhang (Bulletin of Environmental Contamination and Toxicology, 2011)

Functional conservation of the plant EMBRYONIC FLOWER2 gene between bamboo and Arabidopsis - Hong Xu; Ling-Jing Chen; Li-Jia Qu; Hong-Ya Gu; De-Zhu Li (Biotechnology Letters, 2010)

Using FAM labeled DNA oligos to do RNA electrophoretic mobility shift assay - Kun Wang; Ya Gao; Xiaojue Peng; Guohua Yang; Feng Gao; Shaoqing Li; Yingguo Zhu (Molecular Biology Reports, 2010)

Angiotensin-(1–7) and angiotension II in the rostral ventrolateral medulla modulate the cardiac sympathetic afferent reflex and sympathetic activity in rats - Li-Min Zhou; Zhen Shi; Juan Gao; Ying Han; Ning Yuan; Xing-Ya Gao; Guo-Qing Zhu (Pflügers Archiv - European Journal of Physiology, 2010)

Distributions of HLA-A and -B alleles and haplotypes in the Yi ethnic minority of Yunnan, China: relationship to other populations - Bo-feng Zhu; Guang Yang; Chun-mei Shen; Hai-xia Qin; Shun-zhi Liu; Ya-jun Deng; Shuan-liang Fan; Li-bin Deng; Feng Chen; Ping Zhang; Jie Fang; Li-ping Chen; et al. (Journal of Zhejiang University-SCIENCE B, 2010)

Involvement of the ornithine decarboxylase/polyamine system in precondition-induced cardioprotection through an interaction with PKC in rat hearts - Ya-Jun Zhao; Wei-Hua Zhang; Chang-Qing Xu; Hong-Zhu Li; Li-Na Wang; Hong Li; Yi-Hua Sun; Yan Lin; Li-Ping Han; Li Zhang; Yie Tian; Rui Wang; et al. (Molecular and Cellular Biochemistry, 2009)

Evidence for programmed cell death and activation of specific caspase-like enzymes in the tomato fruit heat stress response - Gui-Qin Qu; Xiang Liu; Ya-Li Zhang; Dan Yao; Qiu-Min Ma; Ming-Yu Yang; Wen-Hua Zhu; Shi Yu; Yun-Bo Luo (Planta, 2009)

Expressions of three cotton genes encoding the PIP proteins are regulated in root development and in response to stresses - Deng-Di Li; Ya-Jie Wu; Xiang-Mei Ruan; Bing Li; Li Zhu; Hong Wang; Xue-Bao Li (Plant Cell Reports, 2009)

DETA/NONOate, a nitric oxide donor, produces antidepressant effects by promoting hippocampal neurogenesis - Yao Hua; Xin-Yan Huang; Li Zhou; Qi-Gang Zhou; Yao Hu; Chun-Xia Luo; Fei Li; Dong-Ya Zhu (Psychopharmacology, 2008)

Induction and origin of adventitious shoots from chimeras of Brassica juncea and Brassica oleracea - Xue-Yun Zhu; Man Zhao; Sheng Ma; Ya-Ming Ge; Ming-Fang Zhang; Li-Ping Chen (Plant Cell Reports, 2007)

Expression of a truncated ripening inhibitor (RIN) protein from tomato and production of an anti-RIN antibody - Hong-Liang Zhu; Ben-Zhong Zhu; Ya-Li Zhang; Yi Shao; Xiao-Guang Wang; Yuan-Hong Xie; An-Jun Chen; Ying-Cong Li; Hui-Qin Tian; Yun-Bo Luo (Biotechnology Letters, 2007)

Artificial synthesis of interspecific chimeras between tuber mustard (Brassica juncea) and cabbage (Brassica oleracea) and cytological analysis - Li-Ping Chen; Ya-Ming Ge; Xue-Yun Zhu (Plant Cell Reports, 2006)

Isolation, Characterization and Phylogenetic Analysis of an Aerobic Bacterium Capable of Degrading Bensulfuronmethyl - Ya-Wei Zhu; Yu-Hua Zhao; Xiao-Yan Lin; Li Yang (World Journal of Microbiology and Biotechnology, 2005)

Protective role of selenium against hepatitis B virus and primary liver cancer in Qidong - Shu Yu Yu; Ya Jun Zhu; Wen Gang Li (Biological Trace Element Research, 1997)